Graphene-based conductive textile fabric and preparation method thereof
Through the multilayer structure of composite polyurethane base film, functionalized adhesive layer and modified graphene conductive layer, the shortcomings of conductive textile materials in flexibility, environmental adaptability and multifunctional integration are solved, and the synergistic optimization of high conductivity and mechanical flexibility is achieved, which is suitable for smart wearable devices and medical sensor clothing.
Patent Information
- Application Number
- CN202510825636.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-06-19
AI Technical Summary
Existing conductive textile materials have shortcomings in performance and functional integration, and it is difficult to balance conductivity, flexibility, environmental adaptability and multifunctional integration. In particular, there are problems with biocompatibility and signal stability in the fields of smart wearable devices and medical sensors.
A multilayer structure of a composite polyurethane base film, a functionalized adhesive layer and a modified graphene conductive layer is adopted. The base film is reinforced by stearic acid-modified nano-titanium dioxide, a three-dimensional adhesive network is constructed by carboxylated nanowires, and a core-shell-crosslinked structure is formed by modified graphene, thereby achieving synergistic optimization of conductivity, environmental resistance and mechanical flexibility.
While keeping the fabric soft and breathable, it achieves a balance between the stability of conductive properties and mechanical properties. It is suitable for smart wearable devices, medical sensor clothing and electromagnetic shielding materials, and has significant industrial value.
Smart Images

Figure CN120682520A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of conductive fabrics and relates to a graphene-based conductive textile fabric and a preparation method thereof. Background Art
[0002] With the popularization of smart wearable technology, traditional conductive textile materials are gradually becoming deficient in terms of performance and functional integration. Although metal fibers have excellent conductivity, they are easily oxidized and have poor flexibility. The conductive pathways are easily broken after long-term bending. Conductive polymer materials such as polyaniline are easily affected by environmental temperature and humidity, and there is a risk of molecular degradation. Carbon fiber materials have anisotropic conductive networks due to the disordered distribution of the layers, making it difficult to achieve uniform resistance characteristics. Existing technologies mostly rely on physical coating or chemical vapor deposition. The former sacrifices the breathability and tactile feel of the textile, while the latter is difficult to mass-produce due to the conflict between the high-temperature process and the thermal stability of the fiber, which limits the practical application value of conductive fabrics.
[0003] Graphene, with its single-atomic-layer two-dimensional structure, ultra-high conductivity and mechanical strength, provides a new direction for the construction of new conductive textiles, but its stable bonding with the textile matrix remains a technical difficulty. Conventional solution impregnation methods easily cause the stacking of graphene sheets, forming "island-shaped" conductive areas, and the performance degrades sharply after washing or friction; the process pollution generated by the chemical reduction method goes against the green trend of the textile industry. Existing research focuses on improving conductivity and ignores the mechanical adaptability and functional ductility of textiles, making it difficult for products to take into account derivative functions such as intelligent response and electromagnetic shielding and wearing comfort. The fields of medical monitoring and sports health place higher demands on conductive fabrics: ECG monitoring requires biocompatibility and signal stability, while traditional silver-plated fabrics have the risk of metal ion migration; under dynamic stretching scenarios, the carbon nanotube coating causes resistance drift due to irreversible structural damage, affecting the accuracy of physiological signal acquisition.
[0004] Therefore, there is an urgent need to develop a new process for multi-scale collaboration between graphene and textile fibers, to build a three-dimensional stable conductive network while keeping the fabric soft and breathable, to simultaneously solve core issues such as environmental friendliness, durability and multifunctional integration, and to promote the practical application of smart textiles. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a graphene-based conductive textile fabric and a preparation method thereof. The conductive textile fabric provided by the present invention achieves the synergistic optimization of high conductivity, environmental resistance and mechanical flexibility of the conductive textile fabric through a multilayer composite structure of a composite polyurethane base film, a functionalized adhesive layer and a modified graphene conductive layer. It can be widely used in the fields of smart wearable devices, medical sensor clothing and electromagnetic shielding materials, and has significant industrial value.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a graphene-based conductive textile fabric, the conductive textile fabric comprising a composite polyurethane base film, an adhesive layer, and a modified graphene conductive layer stacked in sequence;
[0008] The composite polyurethane base film is obtained by mixing polyurethane particles, stearic acid-modified nano-titanium dioxide and a lubricant, and then sequentially performing melt extrusion and blow molding to form a film;
[0009] The bonding layer is formed by coating a composite adhesive on the surface of the composite polyurethane base film and then drying and curing it, wherein the composite adhesive includes epoxy resin emulsion, polyvinyl pyrrolidone, curing agent and carboxylated nanowires;
[0010] The modified graphene conductive layer is formed by coating a modified graphene dispersion on the surface of the bonding layer and then drying, curing, and hot pressing. The modified graphene dispersion consists of modified graphene and a composite solvent. The modified graphene is obtained by sequentially subjecting graphene powder to acid activation, dopamine coating modification, glutaraldehyde cross-linking modification, and polyaniline monomer polymerization coating modification.
[0011] The conductive textile fabric provided by the present invention achieves synergistic optimization of high conductivity, environmental resistance, and mechanical flexibility of the conductive textile fabric through a multilayer composite structure of a composite polyurethane base film, a functionalized adhesive layer, and a modified graphene conductive layer. The composite polyurethane base film reinforced with stearic acid-modified nano-titanium dioxide forms a microporous structure during film blow molding, taking into account both air permeability and bending resistance, solving the problem of traditional metal fiber conductive fabrics being stiff and easy to break. The three-dimensional bonding network constructed by carboxylated nanowires and epoxy resin strengthens the interfacial bonding strength between the composite polyurethane base film and the modified graphene conductive layer through the dual effects of chemical bonding and mechanical interlocking, which can effectively resist interlayer delamination caused by repeated bending and water washing. The graphene conductive layer, which has been acid-activated, coated with polydopamine, and polymerized with polyaniline, forms a "core-shell-crosslinked" composite structure, which not only retains the intrinsic high conductivity of graphene, but also suppresses sheet slippage through the flexible polymer coating, thereby realizing a stable conductive network under dynamic stress. The conductive textile fabric obtained by the present invention has excellent conductive and mechanical properties while maintaining the soft touch of natural fabrics. It can be widely used in the fields of smart wearable devices, medical sensor clothing and electromagnetic shielding materials, and has significant industrial value.
[0012] The composite polyurethane base film serves as the base of the entire conductive textile fabric, providing structural support and mechanical buffering for the composite fabric system. Polyurethane itself has good elastic recovery ability, but it is easy to form irreversible deformation during repeated stretching when formed into a film alone. The present invention takes into account both the mechanical strength and flexibility of the base film by introducing stearic acid-modified nano-titanium dioxide particles. The stearic acid-modified nano-titanium dioxide is evenly distributed in the polyurethane molecular chain network, forming a composite structure similar to reinforced concrete. The long-chain alkyl of the stearic acid on the surface of the modified nano-titanium dioxide forms an interpenetrating network with the polyurethane molecular chain through physical entanglement. At the same time, its surface hydroxyl groups form hydrogen bonds with the amino groups in the polyurethane. This dual effect not only enhances the tensile strength of the base film, but also retains the overall flexibility of the material. During the melt extrusion process, the synergistic effect of the lubricant effectively reduces the friction resistance of the molecular chains during the processing process, so that the melt extrusion process can be completed in a relatively mild temperature range, avoiding the influence of high temperature on the heat sensitivity of polyurethane, and ensuring that the surface smoothness of the base film obtained after blow molding meets the requirements for uniform adhesion of the functional coating. The microporous structure formed during the blow molding process allows air to pass through, ensuring the basic moisture permeability and breathability of the fabric. At the same time, the thickness design of 30-40μm not only meets the mechanical support requirements of the base film, but also provides a high-strength and flat support interface for the subsequent functional layer, and avoids the tactile hardening caused by the base film being too thick.
[0013] The adhesive layer primarily connects the composite polyurethane base film to the modified graphene conductive layer. The continuous phase formed by the epoxy resin emulsion forms a three-dimensional cross-linked network upon curing. The addition of polyvinyl pyrrolidone not only improves leveling during coating, but also allows the pyrrolidone rings on the molecular chain to form charge-transfer complexes with amino groups on the polyurethane surface. The introduction of carboxylated nanowires creates a three-dimensional reinforced network. Silicon carbide nanowires, treated with a combined oxidation treatment of hydrogen peroxide and sodium hydroxide, have numerous carboxylic acid groups on their surfaces. One end chemically bonds to the epoxy resin network, while the exposed carboxylic acid groups at the other end provide active sites for the subsequent attachment of the graphene layer. During the coating process, the carboxylated nanowires are partially oriented under the action of shear force, forming vertical conductive microchannels extending from the composite polyurethane base film to the modified graphene conductive layer, providing a high-speed path for charge transfer for the upper graphene conductive network, significantly reducing the anisotropy of in-plane resistance; at the same time, this structural design breaks through the limitations of traditional planar conductive layers. When the fabric is subjected to bending stress, the carboxylated nanowires absorb energy through their own bending deformation, preventing interlayer delamination caused by stress concentration at the interface.
[0014] The modified graphene conductive layer is the core functional layer of conductive textile fabrics. The present invention first introduces oxygen-containing functional groups at the edges of the graphene sheets through acid activation treatment, enhancing the surface reactivity of the graphene material and providing anchoring points for subsequent functional modification. Subsequently, dopamine self-polymerizes to form a polydopamine coating on the graphene surface. Dopamine not only adheres tightly to the graphene surface through π-π stacking, but the strong adhesion generated by its catechol structure also ensures that the polydopamine coating remains intact under mechanical friction. Glutaraldehyde crosslinking establishes covalent bonds between polydopamine molecules, forming a stable three-dimensional network structure that effectively inhibits sliding displacement and stacking agglomeration of the graphene sheets. Finally, under the action of an initiator, aniline monomers are in situ polymerized to construct a conductive polymer coating on the graphene surface. This not only retains the intrinsic high conductivity of graphene, but the outermost polyaniline coating also provides an additional conductive path, enhancing the charge storage capacity through the pseudocapacitive properties of polyaniline, so that the conductive textile fabric can still maintain a stable current output during dynamic stretching.
[0015] The synergistic effect of the three-layer structure achieves a balance between electrical conductivity and mechanical properties. The elastic deformation capacity of the composite polyurethane base film is transferred to the modified graphene conductive layer through the adhesive layer. When the fabric is stretched by external force, the composite polyurethane base film first undergoes molecular chain extension, and the carboxyl nanowires in the adhesive layer subsequently bend and deform. The outermost graphene conductive network remains continuous under the extension of the polyaniline chain segments. This step-by-step deformation mechanism distributes macroscopic stresses throughout the structure, preventing the conductive pathway from breaking due to excessive local stress. The stability of the conductive performance depends on the construction of a multi-scale conductive network. Although the stearic acid-modified nano-titanium dioxide in the composite polyurethane base film is non-conductive, its uniform distribution prevents excessive shrinkage of the polyurethane matrix. The vertical array of carboxyl nanowires in the adhesive layer forms a longitudinal conductive channel throughout the thickness of the adhesive layer, compensating for the anisotropy caused by the horizontal orientation of the graphene sheets. The three-dimensional cross-linked structure of the modified graphene ensures that even if individual sheets break, electrons can still hop through the polyaniline coating for conduction. Furthermore, the synergistic protection of each layer forms a multi-layer barrier that effectively prevents water vapor erosion and ensures that the fabric's electrical conductivity remains high even after multiple washes. The hydrophobic properties of the composite polyurethane base film prevent liquid water from penetrating, while the epoxy resin network in the adhesive layer forms a physical barrier to the diffusion of water molecules. The dense coating structure on the graphene surface prevents moisture from eroding the conductive material. When the fabric comes into contact with sweat or undergoes washing, this layered protection system effectively slows the penetration of water molecules into the conductive material. The introduction of a hot pressing process further strengthens the bonding strength between the layers. The high temperature softens the polyurethane surface layer, causing it to partially embed into the adhesive layer network. Upon cooling, a mechanical interlocking structure is formed. This combined effect of physical anchoring and chemical bonding significantly improves the interlayer peel strength of the fabric.
[0016] As a preferred technical solution of the present invention, the thickness of the composite polyurethane base film is 30 to 40 μm, for example, it can be 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm or 40 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional examples, the thickness of the adhesive layer is 8 to 10 μm, for example, it can be 8.0 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm or 10.0 μm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0018] In some optional examples, the thickness of the modified graphene conductive layer is 10 to 15 μm, for example, it can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0019] In a second aspect, the present invention provides a method for preparing the graphene-based conductive textile fabric according to the first aspect, the preparation method comprising:
[0020] (I) modifying nano-titanium dioxide with stearic acid to obtain modified nano-titanium dioxide, mixing polyurethane particles, the modified nano-titanium dioxide, and a lubricant to obtain a mixture, and sequentially melt-extruding, granulating, and blow-molding the mixture to obtain the composite polyurethane base film;
[0021] (II) modifying silicon carbide nanowires with hydrogen peroxide and sodium hydroxide to obtain carboxylated nanowires; uniformly mixing epoxy resin emulsion, polyvinyl pyrrolidone, the carboxylated nanowires, a curing agent, and deionized water to obtain a composite adhesive, coating the composite adhesive on the surface of the composite polyurethane base film, and forming the adhesive layer after drying and curing;
[0022] (III) activating and modifying the graphene powder using a mixed acid solution, then coating and modifying the graphene powder using a dopamine solution, and finally cross-linking and modifying the graphene powder using a glutaraldehyde solution to obtain cross-linked coated graphene; in-situ polymerizing and coating the cross-linked coated graphene using an aniline monomer and an ammonium persulfate solution to obtain polyaniline-coated modified graphene;
[0023] (IV) dispersing the modified graphene in a composite solvent, stirring at high speed to obtain a modified graphene dispersion, coating the modified graphene dispersion on the surface of the bonding layer, drying, curing and hot pressing to form the modified graphene conductive layer, and obtaining the conductive textile fabric.
[0024] During the preparation of the composite polyurethane-based film, nano-titanium dioxide is surface-treated with stearic acid, significantly improving its compatibility with the polyurethane matrix. The stearic acid molecules encapsulate the nano-titanium dioxide through both physical adsorption and chemical bonding, preventing agglomeration. Furthermore, the long-chain alkyl groups entangle with the polyurethane molecular chains to form an interpenetrating network structure. This modification allows the nano-titanium dioxide to be evenly dispersed during the subsequent melt extrusion process, fully demonstrating its mechanical strengthening effect.
[0025] The present invention introduces carboxylated nanowires as a reinforcing phase in the bonding layer. The surface of the silicon carbide nanowires is selectively oxidized through the synergistic action of hydrogen peroxide and sodium hydroxide, generating carboxylic acid groups in a targeted manner while preserving the structural integrity of the main body of the silicon carbide nanowires. These surface functional groups not only chemically react with the epoxy groups in the epoxy resin but also form a three-dimensional crosslinked network with polyvinyl pyrrolidone through hydrogen bonding. During the coating process, by controlling the drying and curing conditions, the bonding layer forms a gradient crosslinked structure. The area near the composite polyurethane base film forms dense crosslinks to enhance interfacial bonding, while the area near the modified graphene conductive layer maintains moderate crosslinking to maintain elasticity. This gradient structural design enables the bonding layer to withstand the mechanical stress of daily use while providing stable support for the modified graphene conductive layer.
[0026] In the multi-stage modification process of graphene, active sites are first introduced at the edges of the graphene sheets through mixed acid treatment, laying the foundation for subsequent functionalization. The dopamine self-polymerization coating process takes place in a weakly alkaline environment, forming a uniform polydopamine coating on the graphene surface through oxidative self-assembly. This biomimetic adhesion layer not only enhances the environmental stability of graphene but also provides abundant reaction sites. Glutaraldehyde cross-linking treatment establishes covalent bonds between the polydopamines, forming a stable three-dimensional network structure that effectively inhibits the slippage and stacking of the graphene sheets. Finally, the in situ polymerization of polyaniline is carried out under acidic conditions. Aniline monomers grow epitaxially along the cross-linked network, forming a continuous polyaniline conductive coating on the surface of the polydopamine coating. This core-shell structure design not only retains the intrinsic conductive properties of graphene, but also improves the durability of graphene through the protective effect of the outer polymer layer.
[0027] During the coating phase, the present invention employs a specially designed composite solvent for modified graphene. The synergistic effect of sodium dodecylbenzenesulfonate and polyvinylpyrrolidone effectively prevents secondary aggregation of the modified graphene. The optimized mixing ratio of ethanol and water ensures leveling during the spraying process. Adjusting the temperature, pressure, and time of the hot pressing process achieves tight bonding between the layers. The hot pressing temperature of 80-90°C activates molecular motion in the polyurethane surface layer, achieving interfacial fusion while also preventing high temperatures from damaging the modified graphene conductive layer. A hot pressing pressure of 6-8 MPa enables the graphene sheets to be tightly stacked while maintaining their orientation, forming a continuous conductive path.
[0028] As a preferred technical solution of the present invention, in step (I), the modified nano-titanium dioxide is prepared by the following method:
[0029] Stearic acid is dissolved in anhydrous ethanol, mixed, stirred and heated to obtain a stearic acid solution, nano-titanium dioxide and the stearic acid solution are mixed and ball-milled, and then filtered, washed and vacuum-dried to obtain the modified nano-titanium dioxide.
[0030] In some optional examples, the mixing time of the stearic acid and anhydrous ethanol is 40 to 50 minutes, for example, it can be 40 minutes, 41 minutes, 42 minutes, 43 minutes, 44 minutes, 45 minutes, 46 minutes, 47 minutes, 48 minutes, 49 minutes or 50 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] In some optional examples, the temperature for mixing the stearic acid and anhydrous ethanol is 60-70°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0032] In some optional examples, the mass fraction of stearic acid in the stearic acid solution is 3 to 4 wt%, for example, it can be 3.0 wt%, 3.1 wt%, 3.2 wt%, 3.3 wt%, 3.4 wt%, 3.5 wt%, 3.6 wt%, 3.7 wt%, 3.8 wt%, 3.9 wt% or 4.0 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0033] In some optional examples, the mass ratio of the nano-titanium dioxide to the stearic acid in the stearic acid solution is 1:(0.15-0.25), for example, it can be 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24 or 1:0.25, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0034] The present invention specifically limits the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution to 1:(0.15-0.25). Within this ratio, stearic acid molecules chemically bond with hydroxyl groups on the surface of the nano-titanium dioxide through carboxyl groups, forming a monolayer coating structure. The number of stearic acid molecules adsorbed on each nano-titanium dioxide surface reaches saturation coverage, and the long-chain alkyl groups extend outward to form a steric hindrance effect. This modification method ensures uniform dispersion of the nano-titanium dioxide during the polyurethane melt extrusion process, and the long stearic acid chains form physical entanglements with the polyurethane molecular chains, enhancing the interfacial bonding between the modified nano-titanium dioxide and the polyurethane matrix.
[0035] When the amount of stearic acid used is below the lower limit of the range defined in this invention, the stearic acid is insufficient to completely cover the surface of the nano-titanium dioxide. The unmodified nano-titanium dioxide exposes a large number of hydroxyl groups, which can cause severe aggregation during high-temperature processing due to surface energy differences. This leads to the formation of micron-sized aggregates in the polyurethane matrix, which in turn triggers localized stress concentration during the blow molding process and causes microcracks in the composite polyurethane base film. Furthermore, the exposed nano-titanium dioxide surface lacks effective connection to the polyurethane molecular chains, reducing interfacial shear strength and making it susceptible to separation between the nano-titanium dioxide and the polyurethane matrix under external forces.
[0036] When the amount of stearic acid used exceeds the upper limit of the range defined by the present invention, the excess stearic acid molecules form a multi-molecular layer adsorption on the surface of the nano-titanium dioxide. These free stearic acids act as internal lubricants during the melt mixing process, temporarily improving the fluidity of the material. However, after cooling and solidification, a weak interfacial layer is formed between the polyurethane molecular chains. This structural defect reduces the tensile strength of the composite polyurethane base film. Moreover, under high temperature conditions, the stearic acid molecules migrate to the surface to form precipitates, causing the transmittance of the composite polyurethane base film to decrease. In addition, excess stearic acid can also interfere with the microphase separation structure of the polyurethane, reducing the hard segment crystallinity, causing the glass transition temperature of the composite polyurethane base film to decrease, making creep deformation more likely to occur under dynamic loads.
[0037] In some optional examples, the rotation speed of the mixed ball milling of the nano-titanium dioxide and the stearic acid solution is 250-350 rpm, for example, it can be 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm or 350 rpm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0038] In some optional examples, the mixing and ball milling time of the nano-titanium dioxide and the stearic acid solution is 3 to 4 hours, for example, it can be 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In some optional examples, the vacuum drying temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0040] In some optional examples, the vacuum drying time is 8 to 10 hours, for example, it can be 8.0 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9.0 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours or 10.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] As a preferred technical solution of the present invention, in step (I), the mass ratio of the polyurethane particles, the modified nano-titanium dioxide and the lubricant is 100:(8-10):(1.5-2.5), for example, it can be 100:8:1.5, 100:8.2:1.6, 100:8.4:1.7, 100:8.6:1.8, 100:8.8:1.9, 100:9:2, 100:9.2:2.1, 100:9.4:2.2, 100:9.6:2.3, 100:9.8:2.4 or 100:10:2.5, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0042] The present invention specifically limits the mass ratio of polyurethane particles, modified nano-titanium dioxide, and lubricant to 100:(8-10):(1.5-2.5). When the amount of modified nano-titanium dioxide added is within this range, the stearic acid-modified nano-titanium dioxide is uniformly dispersed in the molten polyurethane matrix through the physical entanglement of the surface stearic acid organic long chains with the polyurethane molecular chains. The nano-titanium dioxide acts as a rigidity-reinforcing unit, forming physical crosslinking points in the soft segment region of the polyurethane, thereby improving the creep resistance of the composite material. At the same time, the overall modulus of the composite material is improved through stress transfer in the hard segment region. When an appropriate amount of modified nano-titanium dioxide is added, a stable interpenetrating network is formed in the composite polyurethane base film after blow molding. The modified nano-titanium dioxide neither destroys the microphase separation structure of the polyurethane due to excessive aggregation nor effectively hinders molecular chain slippage through interfacial shearing, thereby being able to withstand the mechanical stress of the subsequent coating process while maintaining the flexible and tough touch required of textile fabrics.
[0043] When the amount of modified nano-titanium dioxide added is lower than the lower limit of the range defined in the present invention, the spatial distribution of the modified nano-titanium dioxide in the polyurethane matrix is too sparse, making it difficult to form a continuous reinforcement network. The physical cross-linking points between the polyurethane molecular chains are insufficient, resulting in a low melt strength of the composite material during the blow molding film-forming stage, and local thinning or bubble breaking is prone to occur during the inflation process. In addition, when the cured composite polyurethane base film is stretched by an external force, the stress cannot be effectively transferred to the modified nano-titanium dioxide, resulting in the mechanical strength of the textile fabric being affected. At the same time, the sparsely distributed modified nano-titanium dioxide weakens its barrier effect on crack propagation, resulting in the composite polyurethane base film being prone to microcracks after repeated bending, which directly affects the adhesion stability of the modified graphene conductive layer on the upper layer, resulting in a decrease in the interlayer bonding strength of the textile fabric.
[0044] When the amount of modified nano-titanium dioxide added exceeds the upper limit of the range defined by the present invention, the excess modified nano-titanium dioxide agglomerates during the melt mixing process due to decreased interfacial compatibility, breaking the steric hindrance effect provided by the stearic acid modified layer. When the agglomerate size exceeds the critical value, it becomes a stress concentration point. These micron-sized agglomerates will hinder the regular arrangement of polyurethane molecular chains during blow molding, destroying the continuity of the hard segment crystalline region, resulting in an abnormal increase in the elastic modulus of the resulting composite polyurethane base film and a sharp decrease in toughness. In addition, excessive modified nano-titanium dioxide will also increase the melt viscosity, requiring higher temperatures or pressures for the blow molding process, exacerbating the risk of thermal degradation of the polyurethane.
[0045] In some optional examples, the lubricant includes calcium stearate and / or zinc stearate.
[0046] In some optional examples, the mixing temperature of the polyurethane particles, the modified nano-titanium dioxide and the lubricant is 130-140°C, for example, it can be 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C or 140°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0047] In some optional examples, the mixing time of the polyurethane particles, the modified nano-titanium dioxide and the lubricant is 40 to 50 minutes, for example, it can be 40 minutes, 41 minutes, 42 minutes, 43 minutes, 44 minutes, 45 minutes, 46 minutes, 47 minutes, 48 minutes, 49 minutes or 50 minutes, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0048] In some optional examples, the melt extrusion of the mixed material is performed in a screw extruder.
[0049] In some optional examples, the barrel of the screw extruder is divided into a first zone, a second zone, and a third zone with different temperatures along the flow direction of the mixed material.
[0050] In some optional examples, the temperature of the first zone is 165-175°C, for example, it can be 165°C, 166°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, 174°C or 175°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0051] In some optional examples, the temperature of the second zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0052] In some optional examples, the temperature of the third zone is 195-205°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0053] In some optional examples, the screw speed of the screw extruder is 35 to 45 rpm, for example, it can be 35 rpm, 36 rpm, 37 rpm, 38 rpm, 39 rpm, 40 rpm, 41 rpm, 42 rpm, 43 rpm, 44 rpm or 45 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the blowing ratio of the blown film is (2.5-3.5):1, for example, it can be 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1 or 3.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the thickness of the composite polyurethane base film is 30 to 40 μm, for example, it can be 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm or 40 μm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0056] As a preferred technical solution of the present invention, in step (II), the carboxylated nanowires are prepared by the following method:
[0057] A hydrogen peroxide solution and a sodium hydroxide solution are uniformly mixed to obtain a modified solution, the silicon carbide nanowires are added to the modified solution, and after ultrasonic dispersion, the solution is transferred to a reactor for high-temperature reaction. After the reaction is completed, the solution is filtered, washed with deionized water, and vacuum dried to obtain the carboxylated nanowires.
[0058] In some optional examples, the mass fraction of the hydrogen peroxide solution is 6 to 8 wt%, for example, it can be 6.0 wt%, 6.2 wt%, 6.4 wt%, 6.6 wt%, 6.8 wt%, 7.0 wt%, 7.2 wt%, 7.4 wt%, 7.6 wt%, 7.8 wt% or 8.0 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0059] In some optional examples, the mass fraction of the sodium hydroxide solution is 7 to 9 wt%, for example, it can be 7.0 wt%, 7.2 wt%, 7.4 wt%, 7.6 wt%, 7.8 wt%, 8.0 wt%, 8.2 wt%, 8.4 wt%, 8.6 wt%, 8.8 wt% or 9.0 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional examples, the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution is 1:(1.3-1.5), for example, it can be 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48 or 1:1.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the mass ratio of the silicon carbide nanowires to the modified solution is 1:(30-40), for example, it can be 1:30, 1:31, 1:32, 1:33, 1:34, 1:35, 1:36, 1:37, 1:38, 1:39 or 1:40, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the silicon carbide nanowires in the modified solution is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the ultrasonic dispersion time of the silicon carbide nanowires in the modified solution is 40 to 50 min, for example, it can be 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min or 50 min, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0064] In some optional examples, the temperature of the high-temperature reaction is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0065] In some optional examples, the high temperature reaction time is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] As a preferred technical solution of the present invention, in step (II), the composite binder is prepared by the following method:
[0067] Epoxy resin emulsion, polyvinyl pyrrolidone and curing agent are added to deionized water, mixed, stirred and heated to obtain a bonding base liquid; then carboxyl nanowires are added to the bonding base liquid, and ultrasonic dispersion is performed to obtain the composite adhesive.
[0068] In some optional examples, the mass ratio of the epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water is (15-17):(1.5-2.5):(3-5):(80-90), for example, it can be 15:1.5:3:80, 15.2:1.6:3.2:81, 15.4:1.7:3.4:82, 15.6:1.8:3.6:83, 15.8:1.9:3.8:84, 16:2:4:85, 16.2:2.1:4.2:86, 16.4:2.2:4.4:87, 16.6:2.3:4.6:88, 16.8:2.4:4.8:89 or 17:2.5:5:90, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the curing agent includes polyetheramine.
[0070] In some optional examples, the mixing and stirring time of the epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water is 30 to 40 minutes, for example, it can be 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0071] In some optional examples, the temperature of mixing and stirring the epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0072] In some optional examples, the mass fraction of the carboxylated nanowires in the composite binder is 3 to 4 wt%, for example, it can be 3.0 wt%, 3.1 wt%, 3.2 wt%, 3.3 wt%, 3.4 wt%, 3.5 wt%, 3.6 wt%, 3.7 wt%, 3.8 wt%, 3.9 wt% or 4.0 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0073] The present invention specifically limits the mass fraction of carboxylated nanowires in the composite adhesive to 3-4wt%. Within this range, the carboxylated nanowires chemically bond with the epoxy groups of the epoxy resin through the abundant carboxylic acid groups on their surface, and are uniformly dispersed in the adhesive layer matrix with the aid of polyvinyl pyrrolidone. During the curing process, the carboxylated nanowires form a three-dimensional network skeleton, and their high axial modulus effectively transmits interlayer stress and improves the shear strength of the adhesive layer. The moderate addition of carboxylated nanowires ensures that the carboxylated nanowires can establish a continuous reinforcement network in the adhesive layer matrix without excessively increasing the viscosity of the system and affecting the coating uniformity of the composite adhesive.
[0074] When the amount of carboxylated nanowires added to the composite adhesive is less than 3wt%, the distribution density of the carboxylated nanowires in the adhesive layer is insufficient to form an effective reinforcement network. The epoxy resin matrix mainly relies on the physical entanglement between the molecular chains to transfer stress, and molecular chain slippage is prone to occur when subjected to shear force. In addition, the large spacing between the carboxylated nanowires makes it impossible to effectively bridge microcracks, and the adhesive layer is prone to through-cracks after repeated bending. At the same time, the number of carboxyl groups is insufficient to fully react with the epoxy resin, resulting in a low cross-linking density of the cured adhesive layer, a significant decrease in solvent resistance and resistance to wet heat aging, and easy interfacial peeling during water washing.
[0075] When the amount of carboxylated nanowires added to the composite adhesive exceeds 4wt%, the excess carboxylated nanowires will locally aggregate in the composite adhesive, especially during the drying stage after coating due to accelerated aggregation due to solvent volatilization. The large-sized aggregates formed will destroy the continuous phase structure of the epoxy resin, forming internal stress concentration points, resulting in a decrease in the strength of the adhesive layer. In addition, the excess carboxylic acid groups compete with the curing agent, resulting in incomplete curing. At the same time, a high content of carboxylated nanowires will also increase the viscosity of the composite adhesive, making it difficult to form a uniform and smooth film layer during transfer coating, resulting in unevenness and pinhole defects on the surface of the adhesive layer obtained by final curing. In addition, the rigid network formed by the excess carboxylated nanowires causes the elastic modulus of the adhesive layer to increase abnormally, making it unable to adapt to the dynamic deformation during use of the textile, and ultimately causing the modified graphene conductive layer to crack or even fall off.
[0076] In some optional examples, the composite adhesive is applied by transfer coating.
[0077] In some optional examples, the coating speed of the composite adhesive is 10 to 12 m / min, for example, it can be 10 m / min, 10.2 m / min, 10.4 m / min, 10.6 m / min, 10.8 m / min, 11 m / min, 11.2 m / min, 11.4 m / min, 11.6 m / min, 11.8 m / min or 12 m / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] In some optional examples, the drying temperature of the composite adhesive after coating is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0079] In some optional examples, the drying time after coating of the composite adhesive is 15 to 25 minutes, for example, it can be 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes or 25 minutes, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0080] In some optional examples, the curing temperature is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In some optional examples, the curing time is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In some optional examples, the thickness of the adhesive layer is 8 to 10 μm, for example, it can be 8.0 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm or 10.0 μm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0083] As a preferred technical solution of the present invention, in step (III), the cross-linked coated graphene is prepared by the following method:
[0084] (1) uniformly mixing a nitric acid solution and a sulfuric acid solution to obtain the mixed acid solution, dispersing the graphene powder in the mixed acid solution, mixing, stirring, and heating to react, and after the reaction is completed, centrifuging, washing with alkaline solution, and vacuum drying to obtain activated graphene;
[0085] (2) dissolving dopamine hydrochloride in a Tris-HCl buffer to obtain a dopamine solution, dispersing the activated graphene in the dopamine solution, mixing and stirring to cause a polymerization reaction, and after the reaction is completed, centrifuging, washing with deionized water, and vacuum drying to obtain a coated graphene with a polydopamine layer on the surface;
[0086] (3) adding glutaraldehyde to a Tris-HCl buffer solution to obtain a glutaraldehyde solution, adding the coated graphene to the glutaraldehyde solution, mixing and stirring to cause a cross-linking reaction, and after the reaction is completed, centrifuging, washing with deionized water, and vacuum drying to obtain the cross-linked coated graphene.
[0087] The present invention enhances the structural stability of graphene while maintaining its conductive properties through multi-stage chemical modification. During the mixed acid treatment stage, the synergistic effect of nitric acid and sulfuric acid selectively introduces oxygen-containing groups at the edges of graphene sheets and surface defects. The generation of these chemical groups enhances the surface activity of graphene. By controlling the reaction time and reaction temperature, excessive damage to the main structure of graphene is avoided. The activated graphene still maintains complete sp 2 The hybrid carbon skeleton provides the main path for electron transfer, while surface functional groups such as carboxyl provide anchoring points for subsequent coating reactions, improving processing performance while maximally retaining its conductivity.
[0088] During the dopamine coating stage, the weakly alkaline environment maintained by the Tris-HCl buffer system promotes the self-polymerization of dopamine molecules on the activated graphene surface. The polydopamine layer tightly bonds to the activated graphene through π-π stacking, with the phenolic hydroxyl groups in its molecular chain forming a hydrogen bond network with the carboxyl groups on the activated graphene surface. This coating structure forms a continuous organic layer on the graphene surface, effectively blocking environmental media from corroding the activated graphene. Furthermore, due to the inherent semiconductor properties of polydopamine, the coating thickness is controlled to the nanometer scale, avoiding complete blockage of electron transitions between graphene sheets. The surface charge adjustment brought about by the polydopamine coating also improves the dispersion stability of graphene in the solution system, facilitating the formation of a uniform conductive network in subsequent processing. Subsequently, glutaraldehyde cross-linking treatment establishes covalent bonds between the polydopamine layers. The condensation reaction between the aldehyde groups and the amino groups forms a three-dimensional network structure. This cross-linking action fixes the relative positions of the graphene sheets, inhibiting slippage or stacking of the graphene sheets due to mechanical stress during use, and maintaining the stability of the conductive path.
[0089] In some optional examples, in step (1), the mass fraction of the nitric acid solution is 65 to 70 wt%, for example, it can be 65 wt%, 65.5 wt%, 66 wt%, 66.5 wt%, 67 wt%, 67.5 wt%, 68 wt%, 68.5 wt%, 69 wt%, 69.5 wt% or 70 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0090] In some optional examples, the mass fraction of the sulfuric acid solution is 95-98wt%, for example, it can be 95wt%, 95.5wt%, 96wt%, 96.5wt%, 97wt%, 97.5wt% or 98wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0091] In some optional examples, the volume ratio of the nitric acid solution to the sulfuric acid solution is 1:(3-4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0092] In some optional examples, the ratio of the graphene powder to the mixed acid solution is 1g:(20-30)L, for example, it can be 1g:20L, 1g:21L, 1g:22L, 1g:23L, 1g:24L, 1g:25L, 1g:26L, 1g:27L, 1g:28L, 1g:29L or 1g:30L, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0093] In some optional examples, the mixing and stirring time of the graphene powder and the mixed acid solution is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0094] In some optional examples, the temperature for mixing and stirring the graphene powder and the mixed acid solution is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0095] In some optional embodiments, in step (2), the pH value of the Tris-HCl buffer is 8 to 9, for example, it can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0096] In some optional examples, the concentration of dopamine hydrochloride in the dopamine solution is 3 to 4 mg / mL, for example, 3.0 mg / mL, 3.1 mg / mL, 3.2 mg / mL, 3.3 mg / mL, 3.4 mg / mL, 3.5 mg / mL, 3.6 mg / mL, 3.7 mg / mL, 3.8 mg / mL, 3.9 mg / mL or 4.0 mg / mL, but is not limited to the listed values, and other values not listed within this numerical range are also applicable.
[0097] In some optional examples, the mass ratio of the activated graphene to the dopamine hydrochloride in the dopamine solution is 1:(1-1.2), for example, it can be 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0098] The present invention specifically limits the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution to 1:(1-1.2). Within this range, dopamine hydrochloride undergoes oxidative self-polymerization under weakly alkaline conditions, synergizing with oxygen-containing groups on the surface of the activated graphene through π-π interactions to form a continuous polydopamine coating layer with a thickness of approximately 5-8 nm. The polydopamine coating layer not only covers the active sites at the edges of the graphene sheets to prevent excessive oxidation, but also forms a stable connection with the subsequent glutaraldehyde cross-linking agent through the amino groups in the molecular chain. The appropriate addition of dopamine ensures that the polydopamine coating layer completely covers the defective areas on the graphene surface, while preventing an excessively thick polydopamine coating layer from completely blocking the electron transition channels between the graphene sheets.
[0099] When the amount of dopamine hydrochloride added is below the lower limit of the range defined by the present invention, the dopamine monomer concentration in the reaction system is insufficient, resulting in localized coverage defects in the polydopamine coating. Uncovered areas on the activated graphene surface are susceptible to excessive crosslinking between the sheets during the subsequent glutaraldehyde crosslinking stage, forming rigid connection points. This non-uniform crosslinking structure causes internal stress concentration in the graphene sheets during the drying process, ultimately leading to microcracks in the conductive network. Furthermore, the exposed graphene edges not coated with polydopamine preferentially adsorb aniline monomer during the polyaniline polymerization stage, triggering localized overpolymerization to form insulating polymer clumps, which disrupt the continuity of the conductive path.
[0100] When the amount of dopamine hydrochloride added exceeds the upper limit of the range defined by the present invention, the excess dopamine monomer forms a dense coating with a thickness exceeding 15nm on the graphene surface. The excessively thick polydopamine coating not only hinders the electron transport of the graphene body, but its own semiconductor properties also add additional resistance to the conductive network. In addition, the free dopamine molecules that are not promptly removed during the polymerization process self-aggregate in the solution to form nanoparticles. These particles randomly adhere to the graphene surface, destroying the uniformity of the polydopamine coating. At the same time, in the subsequent hot pressing process, the interface peeling occurs between the excessively thick polydopamine coating and the polyaniline coating due to the difference in thermal expansion coefficient, resulting in island-like shedding of the modified graphene conductive layer.
[0101] In some optional examples, the mixing and stirring time of the activated graphene and the dopamine solution is 8 to 10 hours, for example, it can be 8.0 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9.0 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours or 10.0 hours, but is not limited to the listed values, and other values not listed within this numerical range are also applicable.
[0102] In some optional examples, the temperature for mixing and stirring the activated graphene and the dopamine solution is 25-35°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other values not listed within this numerical range are also applicable.
[0103] In some optional embodiments, in step (3), the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.5 to 1 wt%, for example, it can be 0.5 wt%, 0.55 wt%, 0.6 wt%, 0.65 wt%, 0.7 wt%, 0.75 wt%, 0.8 wt%, 0.85 wt%, 0.9 wt%, 0.95 wt% or 1 wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0104] In some optional examples, the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:(0.5-0.6), for example, it can be 1:0.5, 1:0.51, 1:0.52, 1:0.53, 1:0.54, 1:0.55, 1:0.56, 1:0.57, 1:0.58, 1:0.59 or 1:0.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0105] In some optional examples, the mixing and stirring time of the coated graphene and the glutaraldehyde solution is 2 to 4 hours, for example, it can be 2.0 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0106] In some optional examples, the temperature for mixing and stirring the coated graphene and the glutaraldehyde solution is 25-35°C, for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0107] As a preferred technical solution of the present invention, in step (III), the modified graphene is prepared by the following method:
[0108] The cross-linked coated graphene is dispersed in a sodium dodecylbenzenesulfonate solution to obtain a cross-linked coated graphene dispersion, a hydrochloric acid solution is dropped into the cross-linked coated graphene dispersion to adjust its pH value, an aniline monomer is added to the cross-linked coated graphene dispersion, and the mixture is evenly mixed to obtain a precursor solution, and an ammonium persulfate solution is dropped into the precursor solution under stirring to cause a monomer polymerization reaction. After the reaction is completed, the mixture is centrifuged, washed with deionized water, and vacuum dried to obtain the modified graphene.
[0109] In some optional examples, the mass fraction of sodium dodecylbenzenesulfonate in the sodium dodecylbenzenesulfonate solution is 0.5 to 1 wt%, for example, it can be 0.5 wt%, 0.55 wt%, 0.6 wt%, 0.65 wt%, 0.7 wt%, 0.75 wt%, 0.8 wt%, 0.85 wt%, 0.9 wt%, 0.95 wt% or 1 wt%, but is not limited to the listed values, and other values not listed within this numerical range are also applicable.
[0110] In some optional examples, the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion is 0.3 to 0.5 mg / mL, for example, it can be 0.3 mg / mL, 0.32 mg / mL, 0.34 mg / mL, 0.36 mg / mL, 0.38 mg / mL, 0.4 mg / mL, 0.42 mg / mL, 0.44 mg / mL, 0.46 mg / mL, 0.48 mg / mL or 0.5 mg / mL, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0111] In some optional examples, a hydrochloric acid solution is added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 1-2, for example, it can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0112] In some optional examples, the concentration of the hydrochloric acid solution is 1 to 2 mol / L, for example, it can be 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2.0 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0113] In some optional examples, the mass ratio of the cross-linked coated graphene in the cross-linked coated graphene dispersion to the aniline monomer is 1:(2-3), for example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.0, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0114] The present invention specifically limits the mass ratio of cross-linked coated graphene to aniline monomer in the cross-linked coated graphene dispersion to 1:(2-3). Within this range, the aniline monomer forms a polyaniline coating layer approximately 10-20 nm thick on the surface of the cross-linked coated graphene through in-situ polymerization. The polyaniline molecular chains are tightly bound to the graphene sheets through π-π conjugation, and their linear molecular structure extends and grows along the surface of the cross-linked coated graphene, forming a continuous conductive path. The appropriate addition of aniline monomer not only establishes a three-dimensional conductive network on the cross-linked coated graphene surface, but also prevents excessive polyaniline from covering the intrinsic conductive regions of the graphene.
[0115] When the amount of aniline monomer used falls below the lower limit of the range specified in this invention, the insufficient aniline monomer concentration in the polymerization reaction system results in a discontinuous, island-like distribution of the polyaniline coating on the surface of the cross-linked graphene. Portions of the cross-linked graphene surface are uncovered by polyaniline, and the exposed oxygen-containing groups easily absorb ambient moisture during subsequent processing, forming an insulating barrier. Furthermore, the sparse polyaniline network cannot effectively bridge adjacent graphene sheets, and the conductive path relies primarily on direct contact between the cross-linked and coated graphene sheets. This structure is prone to localized disconnection during hot pressing due to sheet rearrangement.
[0116] When the amount of aniline monomer exceeds the upper limit of the range defined by the present invention, excess aniline monomer undergoes bulk polymerization during polymerization to form polyaniline particles independent of the cross-linked coated graphene. These free polyaniline particles are not only unable to form an effective conductive connection with the cross-linked coated graphene, but also form insulating isolation zones in the coating. In addition, the overgrown polyaniline coating completely wraps around the graphene sheet, and its thickness significantly hinders the transmission of electrons in the cross-linked coated graphene basal plane after exceeding 30nm, causing the intrinsic conductivity of the cross-linked coated graphene to decline. Simultaneously, excess polyaniline molecular chains produce shrinkage stress during drying and curing, causing microcracks in the modified graphene conductive layer, which has a serious impact on the mechanical properties of textile fabrics.
[0117] In some optional examples, the mixing time of the cross-linked coated graphene dispersion and the aniline monomer is 10 to 15 minutes, for example, it can be 10 minutes, 10.5 minutes, 11 minutes, 11.5 minutes, 12 minutes, 12.5 minutes, 13 minutes, 13.5 minutes, 14 minutes, 14.5 minutes or 15 minutes, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0118] In some optional examples, the mass fraction of the ammonium persulfate solution is 10 to 12 wt%, for example, it can be 10 wt%, 10.2 wt%, 10.4 wt%, 10.6 wt%, 10.8 wt%, 11 wt%, 11.2 wt%, 11.4 wt%, 11.6 wt%, 11.8 wt% or 12 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0119] In some optional examples, the dropping speed of the ammonium persulfate solution is 1 to 2 mL / min, for example, it can be 1.0 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min or 2.0 mL / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0120] In some optional examples, the molar ratio of the aniline monomer to the ammonium persulfate in the ammonium persulfate solution is 1:(1-1.1), for example, 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0121] In some optional examples, after all the ammonium persulfate solution is dropped in, mixing and stirring are continued for 10 to 15 hours, for example, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours or 15 hours, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0122] As a preferred technical solution of the present invention, in step (IV), the composite solvent consists of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, anhydrous ethanol and deionized water.
[0123] In some optional examples, the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 0.8 to 1 wt%, for example, it can be 0.8 wt%, 0.82 wt%, 0.84 wt%, 0.86 wt%, 0.88 wt%, 0.9 wt%, 0.92 wt%, 0.94 wt%, 0.96 wt%, 0.98 wt% or 1 wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0124] In some optional examples, the mass fraction of polyvinylpyrrolidone in the composite solvent is 0.3-0.5wt%, for example, it can be 0.3wt%, 0.32wt%, 0.34wt%, 0.36wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt% or 0.5wt%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0125] In some optional examples, the volume ratio of anhydrous ethanol and deionized water in the composite solvent is 1:(2-3), for example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.0, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0126] In some optional examples, the concentration of the modified graphene in the modified graphene dispersion is 2 to 3 mg / mL, for example, 2.0 mg / mL, 2.1 mg / mL, 2.2 mg / mL, 2.3 mg / mL, 2.4 mg / mL, 2.5 mg / mL, 2.6 mg / mL, 2.7 mg / mL, 2.8 mg / mL, 2.9 mg / mL or 3.0 mg / mL, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0127] In some optional examples, the speed of high-speed stirring of the modified graphene and the composite solvent is 2000-3000 rpm, for example, it can be 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm, 2600 rpm, 2700 rpm, 2800 rpm, 2900 rpm or 3000 rpm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0128] In some optional examples, the time for high-speed stirring of the modified graphene and the composite solvent is 10 to 15 minutes, for example, it can be 10 minutes, 10.5 minutes, 11 minutes, 11.5 minutes, 12 minutes, 12.5 minutes, 13 minutes, 13.5 minutes, 14 minutes, 14.5 minutes or 15 minutes, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0129] In some optional examples, the modified graphene dispersion is coated by reciprocating spraying.
[0130] In some optional examples, the spraying pressure of the modified graphene dispersion is 0.3 to 0.4 MPa, for example, it can be 0.3 MPa, 0.31 MPa, 0.32 MPa, 0.33 MPa, 0.34 MPa, 0.35 MPa, 0.36 MPa, 0.37 MPa, 0.38 MPa, 0.39 MPa or 0.4 MPa, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0131] In some optional examples, the spraying distance of the modified graphene dispersion is 10 to 20 cm, for example, it can be 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, 16 cm, 17 cm, 18 cm, 19 cm or 20 cm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0132] In some optional examples, the modified graphene dispersion is sprayed 3 to 5 times, for example, 3 times, 4 times or 5 times, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0133] In some optional examples, the drying temperature is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0134] In some optional examples, the drying time is 5 to 8 minutes, for example, 5.0 minutes, 5.5 minutes, 6.0 minutes, 6.5 minutes, 7.0 minutes, 7.5 minutes or 8.0 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0135] In some optional examples, the curing temperature is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0136] In some optional examples, the curing time is 3 to 5 minutes, for example, it can be 3.0 minutes, 3.2 minutes, 3.4 minutes, 3.6 minutes, 3.8 minutes, 4.0 minutes, 4.2 minutes, 4.4 minutes, 4.6 minutes, 4.8 minutes or 5.0 minutes, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0137] In some optional examples, the hot pressing temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0138] In some optional examples, the hot pressing time is 10 to 20 seconds, for example, it can be 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds, 15 seconds, 16 seconds, 17 seconds, 18 seconds, 19 seconds or 20 seconds, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0139] In some optional examples, the hot pressing pressure is 6 to 8 MPa, for example, it can be 6.0 MPa, 6.2 MPa, 6.4 MPa, 6.6 MPa, 6.8 MPa, 7.0 MPa, 7.2 MPa, 7.4 MPa, 7.6 MPa, 7.8 MPa or 8.0 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0140] In some optional examples, the thickness of the modified graphene conductive layer is 10 to 15 μm, for example, it can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0141] Compared with the prior art, the present invention has the following beneficial effects:
[0142] The conductive textile fabric provided by the present invention achieves synergistic optimization of high conductivity, environmental resistance, and mechanical flexibility of the conductive textile fabric through a multilayer composite structure of a composite polyurethane base film, a functionalized adhesive layer, and a modified graphene conductive layer. The composite polyurethane base film reinforced with stearic acid-modified nano-titanium dioxide forms a microporous structure during film blow molding, taking into account both air permeability and bending resistance, solving the problem of traditional metal fiber conductive fabrics being stiff and easy to break. The three-dimensional bonding network constructed by carboxylated nanowires and epoxy resin strengthens the interfacial bonding strength between the composite polyurethane base film and the modified graphene conductive layer through the dual effects of chemical bonding and mechanical interlocking, which can effectively resist interlayer delamination caused by repeated bending and water washing. The graphene conductive layer, which has been acid-activated, coated with polydopamine, and polymerized with polyaniline, forms a "core-shell-crosslinked" composite structure, which not only retains the intrinsic high conductivity of graphene, but also suppresses sheet slippage through the flexible polymer coating, thereby realizing a stable conductive network under dynamic stress. The conductive textile fabric obtained by the present invention has excellent conductive and mechanical properties while maintaining the soft touch of natural fabrics. It can be widely used in the fields of smart wearable devices, medical sensor clothing and electromagnetic shielding materials, and has significant industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0143] Figure 1 This is a schematic structural diagram of the conductive textile fabric prepared in Examples 1-15 of the present invention;
[0144] Among them, 1-composite polyurethane base film; 2-adhesive layer; 3-modified graphene conductive layer. DETAILED DESCRIPTION
[0145] The technical solutions of the present invention are described in detail below in conjunction with specific embodiments and the accompanying drawings. The embodiments described herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be understood as limiting the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments described herein. Epoxy resin emulsion: solid content is 40%, model K-051, Shenyang Baichen Chemical Technology Co., Ltd. Polyvinyl pyrrolidone: model XDD6, Wuhan Xindadi Environmental Protection Materials Co., Ltd. Polyetheramine: polyetheramine D-2000, Hubei Jusheng Technology Co., Ltd.
[0146] Example 1
[0147] This embodiment provides a method for preparing a conductive textile fabric, which specifically includes the following steps:
[0148] (1) dissolving stearic acid in anhydrous ethanol, mixing and stirring at 60° C. for 50 min to obtain a stearic acid solution, wherein the mass fraction of stearic acid in the stearic acid solution is 3.0 wt %; mixing nano-titanium dioxide and the stearic acid solution by ball milling, wherein the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is 1:0.15, the rotation speed of the mixing ball milling is 250 rpm, the mixing ball milling time is 4 h, and the material-to-ball ratio of the mixing ball milling is 1:6. After the ball milling is completed, the ball milling product is filtered, and the filtered filter cake is washed with deionized water until it is neutral, and then vacuum dried at 60° C. for 10 h to obtain modified nano-titanium dioxide;
[0149] Polyurethane particles (thermoplastic polyurethane, 85A, purchased from Dongguan Bailing New Materials Co., Ltd.), modified nano-titanium dioxide and calcium stearate were mixed in a mass ratio of 100:8:1.5, and the mixture was stirred at 130° C. for 50 min to obtain a mixture. The mixture was fed into a screw extruder for melt extrusion. The temperature of the first zone of the screw extruder was 165° C., the temperature of the second zone was 180° C., the temperature of the third zone was 195° C., and the screw speed was 35 rpm. After screw extrusion, granulation was performed to obtain a composite masterbatch. The composite masterbatch was blown into a film at a blow-up ratio of 2.5:1 to obtain a composite polyurethane base film 1 with a thickness of 30 μm.
[0150] (2) A 6 wt % hydrogen peroxide solution and a 7 wt % sodium hydroxide solution were mixed, the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution being 1:1.3, and the mixture was uniformly mixed to obtain a modified solution; silicon carbide nanowires (JK-R0746, purchased from Shanghai Jingkang Bioengineering Co., Ltd.) were added to the modified solution, the mass ratio of the silicon carbide nanowires to the modified solution being 1:30, and ultrasonically dispersed at an ultrasonic power of 300 W for 50 min, and then transferred to a reactor for a high-temperature reaction at a temperature of 120° C. for 6 h. After the reaction was completed, the reaction product was filtered, and the filtered filter cake was washed with deionized water until neutral, and then vacuum-dried at 60° C. for 10 h to obtain carboxylated nanowires;
[0151] Epoxy resin emulsion (solid content of 40%, model K-051, purchased from Shenyang Baichen Chemical Technology Co., Ltd.), polyvinyl pyrrolidone (model XDD6, purchased from Wuhan Xindadi Environmental Protection Materials Co., Ltd.) and polyetheramine (polyetheramine D-2000, purchased from Hubei Jusheng Technology Co., Ltd.) were added to deionized water, and the mass ratio of epoxy resin emulsion, polyvinyl pyrrolidone, polyetheramine and deionized water was 15:1.5:3:80. The mixture was mixed and stirred at 40°C for 40 minutes to obtain a bonding base liquid; then carboxylated nanowires were added to the bonding base liquid, and ultrasonic dispersion was performed to obtain a composite adhesive, wherein the mass fraction of carboxylated nanowires in the composite adhesive was 3wt%. The composite adhesive was coated on the surface of a composite polyurethane base film 1 at a coating speed of 10m / min, dried at 70°C for 25 minutes after coating, and then cured at 90°C for 3 hours to form an adhesive layer 2 with a thickness of 8μm on the surface of the composite polyurethane base film 1;
[0152] (3) mixing a nitric acid solution with a mass fraction of 65 wt% and a sulfuric acid solution with a mass fraction of 95 wt% in a volume ratio of 1:3, and uniformly mixing to obtain a mixed acid solution; dispersing graphene powder in the mixed acid solution in a ratio of 1 g:20 L of graphene powder to the mixed acid solution; mixing and stirring at 50 ° C for 3 h to react; centrifuging after the reaction; washing the precipitate after centrifugation with a 1 mol / L sodium hydroxide solution until it is neutral; and then vacuum drying at 60 ° C for 10 h to obtain activated graphene;
[0153] Dopamine hydrochloride is dissolved in a Tris-HCl buffer solution having a pH of 8 to obtain a dopamine solution, wherein the concentration of dopamine hydrochloride in the dopamine solution is 3 mg / mL; activated graphene is dispersed in the dopamine solution, wherein the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is 1:1, and the mixture is mixed and stirred at 25° C. for 10 hours to cause a polymerization reaction. After the reaction is completed, the mixture is centrifuged and separated. The precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 60° C. for 10 hours to obtain coated graphene with a polydopamine layer coated on the surface;
[0154] Glutaraldehyde is added to a Tris-HCl buffer solution having a pH of 8 to obtain a glutaraldehyde solution, wherein the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.5 wt %; the coated graphene is added to the glutaraldehyde solution, wherein the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:0.5; the mixture is mixed and stirred at 25° C. for 4 hours to cause a cross-linking reaction; after the reaction is completed, the mixture is centrifuged; the precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 60° C. for 10 hours to obtain the cross-linked coated graphene;
[0155] The cross-linked coated graphene was dispersed in a sodium dodecylbenzenesulfonate solution with a mass fraction of 0.5 wt % to obtain a cross-linked coated graphene dispersion, wherein the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion was 0.3 mg / mL; a 1 mol / L hydrochloric acid solution was added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 2; an aniline monomer was added to the cross-linked coated graphene dispersion, wherein the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion was 1:2; and the mixture was stirred. After stirring for 10 minutes, a precursor solution was obtained. Under stirring conditions, a 10 wt% ammonium persulfate solution was added dropwise to the precursor solution at a dropping rate of 1 mL / min. The molar ratio of aniline monomer to ammonium persulfate in the ammonium persulfate solution was 1:1. After all the ammonium persulfate solution was dropped, the mixture was continued to be mixed and stirred for 10 hours to allow monomer polymerization to occur. After the reaction was completed, the mixture was centrifuged and the precipitate was washed with deionized water until it was neutral. It was then vacuum dried at 60° C. for 10 hours to obtain modified graphene.
[0156] (4) Sodium dodecylbenzenesulfonate, polyvinylpyrrolidone (model XDD6, purchased from Wuhan Xindadi Environmental Protection Materials Co., Ltd.), anhydrous ethanol and deionized water were mixed uniformly to obtain a composite solvent, wherein the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent was 0.8wt%, the mass fraction of polyvinylpyrrolidone was 0.3wt%, and the volume ratio of anhydrous ethanol to deionized water was 1:2; the modified graphene was dispersed in the composite solvent and stirred at a speed of 2000 rpm for 15 min to obtain a modified graphene dispersion, wherein the concentration of the modified graphene in the modified graphene dispersion was 2 mg / mL;
[0157] The modified graphene dispersion was sprayed reciprocatingly on the surface of the bonding layer 2. The spraying pressure of the modified graphene dispersion was 0.3 MPa, the spraying distance was 10 cm, and the number of spraying was 3 times. After spraying, it was dried at 50°C for 8 minutes, then cured at 90°C for 5 minutes, and finally hot pressed at 80°C and a pressure of 6 MPa for 20 seconds to form a modified graphene conductive layer 3 with a thickness of 10 μm on the surface of the bonding layer 2. Figure 1 The conductive textile fabric shown.
[0158] Example 2
[0159] This embodiment provides a method for preparing a conductive textile fabric, which specifically includes the following steps:
[0160] (1) dissolving stearic acid in anhydrous ethanol, mixing and stirring at 62° C. for 48 minutes to obtain a stearic acid solution, wherein the mass fraction of stearic acid in the stearic acid solution is 3.2 wt %; mixing nano-titanium dioxide and the stearic acid solution by ball milling, wherein the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is 1:0.18, the rotation speed of the mixing ball milling is 280 rpm, the mixing ball milling time is 3.8 hours, and the material-ball ratio of the mixing ball milling is 1:6.5. After the ball milling is completed, the ball milling product is filtered, and the filtered filter cake is washed with deionized water until it is neutral, and then vacuum dried at 62° C. for 9.5 hours to obtain modified nano-titanium dioxide;
[0161] Polyurethane particles, modified nano-titanium dioxide, and calcium stearate were mixed in a mass ratio of 100:8.5:1.8, and the mixture was stirred at 132° C. for 48 minutes to obtain a mixture. The mixture was fed into a screw extruder for melt extrusion. The temperature of the first zone of the screw extruder was 168° C., the temperature of the second zone was 182° C., the temperature of the third zone was 198° C., and the screw speed was 38 rpm. After screw extrusion, granulation was performed to obtain a composite masterbatch. The composite masterbatch was blown into a film at a blow-up ratio of 2.8:1 to obtain a composite polyurethane base film 1 with a thickness of 32 μm.
[0162] (2) A 6.5 wt% hydrogen peroxide solution and a 7.5 wt% sodium hydroxide solution were mixed, the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution being 1:1.35, and the mixture was uniformly mixed to obtain a modified solution; silicon carbide nanowires were added to the modified solution, the mass ratio of the silicon carbide nanowires to the modified solution being 1:32, and ultrasonically dispersed at an ultrasonic power of 320 W for 48 minutes, and then transferred to a reactor for a high-temperature reaction at a temperature of 122° C. and a high-temperature reaction time of 5.8 hours. After the reaction was completed, the reaction product was filtered, and the filtered filter cake was washed with deionized water until it was neutral, and then vacuum dried at 62° C. for 9.5 hours to obtain carboxylated nanowires;
[0163] Epoxy resin emulsion, polyvinyl pyrrolidone and polyether amine are added to deionized water in a mass ratio of 15.5:1.8:3.5:82, and the mixture is mixed and stirred at 42° C. for 38 minutes to obtain a bonding base liquid; carboxylated nanowires are then added to the bonding base liquid, and ultrasonic dispersion is performed to obtain a composite adhesive, wherein the mass fraction of the carboxylated nanowires in the composite adhesive is 3.2 wt %. The composite adhesive is applied to the surface of a composite polyurethane base film 1 at a coating speed of 10.5 m / min, dried at 72° C. for 22 minutes after coating, and then cured at 92° C. for 2.8 hours to form an adhesive layer 2 with a thickness of 8.5 μm on the surface of the composite polyurethane base film 1;
[0164] (3) mixing a nitric acid solution with a mass fraction of 66 wt% and a sulfuric acid solution with a mass fraction of 96 wt%, wherein the volume ratio of the nitric acid solution to the sulfuric acid solution is 1:3.2, and uniformly mixing to obtain a mixed acid solution; dispersing graphene powder in the mixed acid solution; wherein the ratio of the graphene powder to the mixed acid solution is 1 g:22 L; mixing and stirring at 52 ° C for 2.8 h to react; after the reaction is completed, centrifuging and separating; washing the precipitate after centrifugation with a 1 mol / L sodium hydroxide solution until it is neutral; and then vacuum drying at 62 ° C for 9.5 h to obtain activated graphene;
[0165] Dopamine hydrochloride is dissolved in a Tris-HCl buffer solution having a pH of 8.2 to obtain a dopamine solution, wherein the concentration of dopamine hydrochloride in the dopamine solution is 3.2 mg / mL; activated graphene is dispersed in the dopamine solution, wherein the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is 1:1.05, and the mixture is mixed and stirred at 28° C. for 9.5 hours to cause a polymerization reaction. After the reaction is completed, the mixture is centrifuged and separated. The precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 62° C. for 9.5 hours to obtain coated graphene with a polydopamine layer coated on the surface;
[0166] Glutaraldehyde is added to a Tris-HCl buffer solution having a pH value of 8.2 to obtain a glutaraldehyde solution, wherein the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.6 wt %; the coated graphene is added to the glutaraldehyde solution, wherein the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:0.52; the mixture is mixed and stirred at 28° C. for 3.5 hours to cause a cross-linking reaction; after the reaction is completed, the mixture is centrifuged and separated; the precipitate after centrifugation is washed with deionized water until it is neutral; and then vacuum dried at 62° C. for 9.5 hours to obtain the cross-linked coated graphene;
[0167] The cross-linked coated graphene was dispersed in a sodium dodecylbenzenesulfonate solution with a mass fraction of 0.6 wt % to obtain a cross-linked coated graphene dispersion, wherein the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion was 0.35 mg / mL; a 1.2 mol / L hydrochloric acid solution was added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 1.8, and aniline monomer was added to the cross-linked coated graphene dispersion, wherein the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion was 1:2.2, and the mixture was stirred. After 11 minutes, a precursor solution was obtained. Under stirring conditions, a 10.5 wt% ammonium persulfate solution was added dropwise to the precursor solution at a dropping rate of 1.2 mL / min. The molar ratio of aniline monomer to ammonium persulfate in the ammonium persulfate solution was 1:1.02. After all the ammonium persulfate solution was dropped, mixing and stirring were continued for 11 hours to allow monomer polymerization to occur. After the reaction was completed, centrifugation was performed, and the precipitate after centrifugation was washed with deionized water until neutral, and then vacuum dried at 62° C. for 9.5 hours to obtain modified graphene;
[0168] (4) Sodium dodecylbenzenesulfonate, polyvinyl pyrrolidone, anhydrous ethanol and deionized water are uniformly mixed to obtain a composite solvent, wherein the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 0.85wt%, the mass fraction of polyvinyl pyrrolidone is 0.35wt%, and the volume ratio of anhydrous ethanol to deionized water is 1:2.2; the modified graphene is dispersed in the composite solvent, and stirred at a speed of 2200 rpm for 13 min to obtain a modified graphene dispersion, wherein the concentration of the modified graphene in the modified graphene dispersion is 2.2 mg / mL;
[0169] The modified graphene dispersion was sprayed reciprocatingly on the surface of the bonding layer 2. The spraying pressure of the modified graphene dispersion was 0.32 MPa, the spraying distance was 12 cm, and the number of spraying was 3. After spraying, it was dried at 52°C for 7 minutes, then cured at 92°C for 4.5 minutes, and finally hot pressed at 82°C and a pressure of 6.5 MPa for 18 seconds to form a modified graphene conductive layer 3 with a thickness of 11 μm on the surface of the bonding layer 2. Figure 1 The conductive textile fabric shown.
[0170] Example 3
[0171] This embodiment provides a method for preparing a conductive textile fabric, which specifically includes the following steps:
[0172] (1) dissolving stearic acid in anhydrous ethanol, mixing and stirring at 65° C. for 45 minutes to obtain a stearic acid solution, wherein the mass fraction of stearic acid in the stearic acid solution is 3.5 wt%; mixing nano-titanium dioxide and the stearic acid solution by ball milling, wherein the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is 1:0.2, the speed of the mixing ball milling is 300 rpm, the mixing ball milling time is 3.5 hours, and the material-ball ratio of the mixing ball milling is 1:7. After the ball milling is completed, the ball milling product is filtered, and the filtered filter cake is washed with deionized water until it is neutral, and then vacuum dried at 65° C. for 9 hours to obtain modified nano-titanium dioxide;
[0173] Polyurethane particles, modified nano-titanium dioxide, and zinc stearate were mixed in a mass ratio of 100:9:2, and the mixture was stirred at 135° C. for 45 minutes to obtain a mixture. The mixture was fed into a screw extruder for melt extrusion. The temperature of the first zone of the screw extruder was 170° C., the temperature of the second zone was 185° C., the temperature of the third zone was 200° C., and the screw speed was 40 rpm. After screw extrusion, granulation was performed to obtain a composite masterbatch. The composite masterbatch was blown into a film at a blow-up ratio of 3:1 to obtain a composite polyurethane base film 1 with a thickness of 35 μm.
[0174] (2) A 7wt% hydrogen peroxide solution and an 8wt% sodium hydroxide solution were mixed, the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution being 1:1.4, and the mixture was uniformly mixed to obtain a modified solution; silicon carbide nanowires were added to the modified solution, the mass ratio of the silicon carbide nanowires to the modified solution being 1:35, and ultrasonically dispersed at an ultrasonic power of 350W for 45 minutes, and then transferred to a reactor for a high-temperature reaction at a temperature of 125°C for 5.5 hours. After the reaction was completed, the reaction product was filtered, and the filtered filter cake was washed with deionized water until it was neutral, and then vacuum dried at 65°C for 9 hours to obtain carboxylated nanowires;
[0175] An epoxy resin emulsion, polyvinyl pyrrolidone, and polyetheramine were added to deionized water in a mass ratio of 16:2:4:85, and the mixture was stirred at 45° C. for 35 minutes to obtain a bonding base liquid. Carboxylated nanowires were then added to the bonding base liquid, and ultrasonic dispersion was performed to obtain a composite adhesive, wherein the mass fraction of the carboxylated nanowires in the composite adhesive was 3.5 wt %. The composite adhesive was applied to a surface of a composite polyurethane base film 1 at a coating speed of 11 m / min, dried at 75° C. for 20 minutes, and then cured at 95° C. for 2.5 hours to form a bonding layer 2 with a thickness of 9 μm on the surface of the composite polyurethane base film 1.
[0176] (3) a nitric acid solution with a mass fraction of 67 wt% and a sulfuric acid solution with a mass fraction of 96 wt% were mixed, the volume ratio of the nitric acid solution to the sulfuric acid solution being 1:3.5, and the mixed solution was uniformly obtained to obtain a mixed acid solution, graphene powder was dispersed in the mixed acid solution, the ratio of the graphene powder to the mixed acid solution was 1 g:25 L, and the mixture was stirred at 55 ° C for 2.5 h to react, and after the reaction was completed, the mixture was centrifuged and the precipitate was washed with a 1 mol / L sodium hydroxide solution until it was neutral, and then vacuum dried at 65 ° C for 9 h to obtain activated graphene;
[0177] Dopamine hydrochloride is dissolved in a Tris-HCl buffer solution having a pH value of 8.5 to obtain a dopamine solution, wherein the concentration of dopamine hydrochloride in the dopamine solution is 3.5 mg / mL; activated graphene is dispersed in the dopamine solution, wherein the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is 1:1.1, and the mixture is mixed and stirred at 30° C. for 9 hours to cause a polymerization reaction. After the reaction is completed, the mixture is centrifuged and separated. The precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 65° C. for 9 hours to obtain coated graphene with a polydopamine layer coated on the surface;
[0178] Glutaraldehyde is added to a Tris-HCl buffer solution having a pH value of 8.5 to obtain a glutaraldehyde solution, wherein the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.7 wt %; the coated graphene is added to the glutaraldehyde solution, wherein the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:0.55; the mixture is mixed and stirred at 30° C. for 3 hours to cause a cross-linking reaction; after the reaction is completed, the mixture is centrifuged and separated; the precipitate after centrifugation is washed with deionized water until it is neutral; and then vacuum dried at 65° C. for 9 hours to obtain the cross-linked coated graphene;
[0179] The cross-linked coated graphene was dispersed in a sodium dodecylbenzenesulfonate solution with a mass fraction of 0.7 wt % to obtain a cross-linked coated graphene dispersion, wherein the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion was 0.4 mg / mL; a 1.5 mol / L hydrochloric acid solution was added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 1.5; an aniline monomer was added to the cross-linked coated graphene dispersion, wherein the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion was 1:2.5; and the mixture was stirred for 2 hours. After stirring for 12 minutes, a precursor solution was obtained. Under stirring conditions, an ammonium persulfate solution with a mass fraction of 11 wt% was added dropwise to the precursor solution at a dropping rate of 1.5 mL / min. The molar ratio of aniline monomer to ammonium persulfate in the ammonium persulfate solution was 1:1.05. After all the ammonium persulfate solution was dropped, the mixture was mixed and stirred for 12 hours to allow the monomer polymerization reaction to occur. After the reaction was completed, the mixture was centrifuged and the precipitate after centrifugation was washed with deionized water until it was neutral, and then vacuum dried at 65° C. for 9 hours to obtain modified graphene.
[0180] (4) Sodium dodecylbenzenesulfonate, polyvinyl pyrrolidone, anhydrous ethanol and deionized water are uniformly mixed to obtain a composite solvent, wherein the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 0.9 wt %, the mass fraction of polyvinyl pyrrolidone is 0.4 wt %, and the volume ratio of anhydrous ethanol to deionized water is 1:2.5; the modified graphene is dispersed in the composite solvent, and stirred at a speed of 2500 rpm for 12 min to obtain a modified graphene dispersion, wherein the concentration of the modified graphene in the modified graphene dispersion is 2.5 mg / mL;
[0181] The modified graphene dispersion was sprayed reciprocatingly on the surface of the bonding layer 2. The spraying pressure of the modified graphene dispersion was 0.35 MPa, the spraying distance was 15 cm, and the number of spraying was 4 times. After spraying, it was dried at 55°C for 6 minutes, then cured at 95°C for 4 minutes, and finally hot pressed at 85°C and a pressure of 7 MPa for 15 seconds to form a modified graphene conductive layer 3 with a thickness of 12 μm on the surface of the bonding layer 2. Figure 1 The conductive textile fabric shown.
[0182] Example 4
[0183] This embodiment provides a method for preparing a conductive textile fabric, which specifically includes the following steps:
[0184] (1) dissolving stearic acid in anhydrous ethanol, mixing and stirring at 68° C. for 42 minutes to obtain a stearic acid solution, wherein the mass fraction of stearic acid in the stearic acid solution is 3.8 wt %; mixing nano-titanium dioxide and the stearic acid solution by ball milling, wherein the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is 1:0.22, the rotation speed of the mixing ball milling is 320 rpm, the mixing ball milling time is 3.2 hours, and the material-ball ratio of the mixing ball milling is 1:7.5. After the ball milling is completed, the ball milling product is filtered, and the filtered filter cake is washed with deionized water until it is neutral, and then vacuum dried at 68° C. for 8.5 hours to obtain modified nano-titanium dioxide;
[0185] Polyurethane particles, modified nano-titanium dioxide, and zinc stearate were mixed in a mass ratio of 100:9.5:2.2, and the mixture was stirred at 138° C. for 42 minutes to obtain a mixture. The mixture was fed into a screw extruder for melt extrusion. The temperature of the first zone of the screw extruder was 172° C., the temperature of the second zone was 188° C., the temperature of the third zone was 202° C., and the screw speed was 42 rpm. After screw extrusion, granulation was performed to obtain a composite masterbatch. The composite masterbatch was blown into a film at a blow-up ratio of 3.2:1 to obtain a composite polyurethane base film 1 with a thickness of 38 μm.
[0186] (2) A 7.5 wt% hydrogen peroxide solution and an 8.5 wt% sodium hydroxide solution were mixed, the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution being 1:1.45, and the mixture was uniformly mixed to obtain a modified solution; silicon carbide nanowires were added to the modified solution, the mass ratio of the silicon carbide nanowires to the modified solution being 1:38, and ultrasonically dispersed at an ultrasonic power of 380 W for 42 minutes, and then transferred to a reactor for a high-temperature reaction at a temperature of 128° C. for 5.2 hours. After the reaction was completed, the reaction product was filtered, and the filtered filter cake was washed with deionized water until it was neutral, and then vacuum dried at 68° C. for 8.5 hours to obtain carboxylated nanowires;
[0187] Epoxy resin emulsion, polyvinyl pyrrolidone and polyether amine are added to deionized water in a mass ratio of 16.5:2.2:4.5:88, and the mixture is mixed and stirred at 48°C for 32 minutes to obtain a bonding base liquid; carboxylated nanowires are then added to the bonding base liquid, and ultrasonic dispersion is performed to obtain a composite adhesive, wherein the mass fraction of the carboxylated nanowires in the composite adhesive is 3.8wt%. The composite adhesive is applied to the surface of a composite polyurethane base film 1 at a coating speed of 11.5 m / min, dried at 78°C for 18 minutes after coating, and then cured at 98°C for 2.2 hours to form a bonding layer 2 with a thickness of 9.5 μm on the surface of the composite polyurethane base film 1;
[0188] (3) mixing a nitric acid solution with a mass fraction of 68 wt% and a sulfuric acid solution with a mass fraction of 97 wt% in a volume ratio of 1:3.8, and uniformly mixing to obtain a mixed acid solution; dispersing graphene powder in the mixed acid solution in a ratio of 1 g:28 L of graphene powder to the mixed acid solution; stirring the mixture at 58 ° C for 2.2 h to react; centrifuging after the reaction; washing the precipitate after centrifugation with a 1 mol / L sodium hydroxide solution until it is neutral; and then vacuum drying at 68 ° C for 8.5 h to obtain activated graphene;
[0189] Dopamine hydrochloride is dissolved in a Tris-HCl buffer solution having a pH value of 8.8 to obtain a dopamine solution, wherein the concentration of dopamine hydrochloride in the dopamine solution is 3.8 mg / mL; activated graphene is dispersed in the dopamine solution, wherein the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is 1:1.15, and the mixture is mixed and stirred at 32° C. for 8.5 hours to cause a polymerization reaction. After the reaction is completed, the mixture is centrifuged and separated. The precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 68° C. for 8.5 hours to obtain coated graphene with a polydopamine layer coated on the surface;
[0190] Glutaraldehyde is added to a Tris-HCl buffer solution having a pH value of 8.8 to obtain a glutaraldehyde solution, wherein the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.8 wt %; the coated graphene is added to the glutaraldehyde solution, wherein the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:0.58, and the mixture is mixed and stirred at 32° C. for 2.5 hours to cause a cross-linking reaction. After the reaction is completed, the mixture is centrifuged and separated, and the precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 68° C. for 8.5 hours to obtain the cross-linked coated graphene;
[0191] The cross-linked coated graphene was dispersed in a sodium dodecylbenzenesulfonate solution with a mass fraction of 0.8 wt % to obtain a cross-linked coated graphene dispersion, wherein the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion was 0.45 mg / mL; a 1.8 mol / L hydrochloric acid solution was added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 1.2, and aniline monomer was added to the cross-linked coated graphene dispersion, wherein the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion was 1:2.8, and the mixture was stirred. After 13 minutes, a precursor solution was obtained. Under stirring conditions, an ammonium persulfate solution with a mass fraction of 11.5 wt% was added dropwise to the precursor solution at a dropping rate of 1.8 mL / min. The molar ratio of aniline monomer to ammonium persulfate in the ammonium persulfate solution was 1:1.08. After all the ammonium persulfate solution was dropped, mixing and stirring were continued for 13 hours to allow monomer polymerization to occur. After the reaction was completed, centrifugation was performed, and the precipitate after centrifugation was washed with deionized water until neutral, and then vacuum dried at 68° C. for 8.5 hours to obtain modified graphene;
[0192] (4) Sodium dodecylbenzenesulfonate, polyvinyl pyrrolidone, anhydrous ethanol and deionized water are uniformly mixed to obtain a composite solvent, wherein the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 0.95wt%, the mass fraction of polyvinyl pyrrolidone is 0.45wt%, and the volume ratio of anhydrous ethanol to deionized water is 1:2.8; the modified graphene is dispersed in the composite solvent, and stirred at a speed of 2800 rpm for 11 minutes to obtain a modified graphene dispersion, wherein the concentration of the modified graphene in the modified graphene dispersion is 2.8 mg / mL;
[0193] The modified graphene dispersion was sprayed reciprocatingly on the surface of the bonding layer 2. The spraying pressure of the modified graphene dispersion was 0.38 MPa, the spraying distance was 18 cm, and the number of spraying was 4 times. After spraying, it was dried at 58°C for 6 minutes, then cured at 98°C for 3.5 minutes, and finally hot pressed at 88°C and a pressure of 7.5 MPa for 12 seconds to form a modified graphene conductive layer 3 with a thickness of 13 μm on the surface of the bonding layer 2. Figure 1 The conductive textile fabric shown.
[0194] Example 5
[0195] This embodiment provides a method for preparing a conductive textile fabric, which specifically includes the following steps:
[0196] (1) dissolving stearic acid in anhydrous ethanol, mixing and stirring at 70° C. for 40 min to obtain a stearic acid solution, wherein the mass fraction of stearic acid in the stearic acid solution is 4 wt %; mixing nano-titanium dioxide and the stearic acid solution by ball milling, wherein the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is 1:0.25, the speed of the mixing ball milling is 350 rpm, the mixing ball milling time is 3 h, and the material-ball ratio of the mixing ball milling is 1:8. After the ball milling is completed, the ball milling product is filtered, and the filtered filter cake is washed with deionized water until it is neutral, and then vacuum dried at 70° C. for 8 h to obtain modified nano-titanium dioxide;
[0197] Polyurethane particles, modified nano-titanium dioxide, and zinc stearate were mixed in a mass ratio of 100:10:2.5, and the mixture was stirred at 140° C. for 40 min to obtain a mixture. The mixture was fed into a screw extruder for melt extrusion. The temperature of the first zone of the screw extruder was 175° C., the temperature of the second zone was 190° C., the temperature of the third zone was 205° C., and the screw speed was 45 rpm. After screw extrusion, granulation was performed to obtain a composite masterbatch. The composite masterbatch was blown into a film at a blow-up ratio of 3.5:1 to obtain a composite polyurethane base film 1 with a thickness of 40 μm.
[0198] (2) A hydrogen peroxide solution with a mass fraction of 8 wt% and a sodium hydroxide solution with a mass fraction of 9 wt% were mixed, and the volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution was 1:1.5. After uniform mixing, a modified solution was obtained; silicon carbide nanowires were added to the modified solution, and the mass ratio of the silicon carbide nanowires to the modified solution was 1:40. The solution was ultrasonically dispersed at an ultrasonic power of 400 W for 40 minutes, and then transferred to a reactor for a high-temperature reaction at a temperature of 130°C and a time of 5 hours. After the reaction was completed, the reaction product was filtered, and the filter cake after the filtration was washed with deionized water until it was neutral, and then vacuum dried at 70°C for 8 hours to obtain carboxylated nanowires;
[0199] An epoxy resin emulsion, polyvinyl pyrrolidone, and polyetheramine were added to deionized water in a mass ratio of 17:2.5:5:90, and the mixture was stirred at 50° C. for 30 minutes to obtain a bonding base liquid. Carboxylated nanowires were then added to the bonding base liquid, and ultrasonic dispersion was performed to obtain a composite adhesive, wherein the mass fraction of the carboxylated nanowires in the composite adhesive was 4 wt %. The composite adhesive was applied to a surface of a composite polyurethane base film 1 at a coating speed of 12 m / min, dried at 80° C. for 15 minutes, and then cured at 100° C. for 2 hours to form a bonding layer 2 with a thickness of 10 μm on the surface of the composite polyurethane base film 1.
[0200] (3) mixing a nitric acid solution with a mass fraction of 70 wt% and a sulfuric acid solution with a mass fraction of 98 wt% in a volume ratio of 1:4, and uniformly mixing to obtain a mixed acid solution; dispersing graphene powder in the mixed acid solution in a ratio of 1 g:30 L of graphene powder to the mixed acid solution; stirring the mixture at 60 ° C for 2 h to react; centrifuging after the reaction; washing the precipitate after centrifugation with a 1 mol / L sodium hydroxide solution until it is neutral; and then vacuum drying at 70 ° C for 8 h to obtain activated graphene;
[0201] Dopamine hydrochloride is dissolved in a Tris-HCl buffer solution having a pH of 9 to obtain a dopamine solution, wherein the concentration of dopamine hydrochloride in the dopamine solution is 4 mg / mL; activated graphene is dispersed in the dopamine solution, wherein the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is 1:1.2, and the mixture is mixed and stirred at 35° C. for 8 hours to cause a polymerization reaction. After the reaction is completed, the mixture is centrifuged and separated. The precipitate after centrifugation is washed with deionized water until it is neutral, and then vacuum dried at 70° C. for 8 hours to obtain coated graphene with a polydopamine layer coated on the surface;
[0202] Glutaraldehyde is added to a Tris-HCl buffer solution having a pH of 9 to obtain a glutaraldehyde solution, wherein the mass fraction of glutaraldehyde in the glutaraldehyde solution is 1 wt %; the coated graphene is added to the glutaraldehyde solution, wherein the mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:0.6; the mixture is mixed and stirred at 35° C. for 2 hours to cause a cross-linking reaction; after the reaction is completed, the mixture is centrifuged and separated; the precipitate after centrifugation is washed with deionized water until it is neutral; and then vacuum dried at 70° C. for 8 hours to obtain the cross-linked coated graphene;
[0203] The cross-linked coated graphene was dispersed in a sodium dodecylbenzenesulfonate solution with a mass fraction of 1 wt % to obtain a cross-linked coated graphene dispersion, wherein the concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion was 0.5 mg / mL; a 2 mol / L hydrochloric acid solution was added dropwise to the cross-linked coated graphene dispersion to adjust its pH value to 1, and aniline monomer was added to the cross-linked coated graphene dispersion, wherein the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion was 1:3, and the mixture was stirred for 1 hr. After 5 minutes, a precursor solution was obtained. Under stirring conditions, a 12 wt% ammonium persulfate solution was added dropwise to the precursor solution at a dropping rate of 2 mL / min. The molar ratio of aniline monomer to ammonium persulfate in the ammonium persulfate solution was 1:1.1. After all the ammonium persulfate solution was dropped, the mixture was mixed and stirred for 15 hours to allow monomer polymerization to occur. After the reaction was completed, the mixture was centrifuged and the precipitate was washed with deionized water until it was neutral. It was then vacuum dried at 70°C for 8 hours to obtain modified graphene.
[0204] (4) Sodium dodecylbenzenesulfonate, polyvinyl pyrrolidone, anhydrous ethanol and deionized water are uniformly mixed to obtain a composite solvent, wherein the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 1 wt %, the mass fraction of polyvinyl pyrrolidone is 0.5 wt %, and the volume ratio of anhydrous ethanol to deionized water is 1:3; the modified graphene is dispersed in the composite solvent, and stirred at a speed of 3000 rpm for 10 min to obtain a modified graphene dispersion, wherein the concentration of the modified graphene in the modified graphene dispersion is 3 mg / mL;
[0205] The modified graphene dispersion was sprayed reciprocatingly on the surface of the bonding layer 2. The spraying pressure of the modified graphene dispersion was 0.4 MPa, the spraying distance was 20 cm, and the number of spraying was 5 times. After spraying, it was dried at 60°C for 5 minutes, then cured at 100°C for 3 minutes, and finally hot pressed at 90°C and 8 MPa for 10 seconds to form a modified graphene conductive layer 3 with a thickness of 15 μm on the surface of the bonding layer 2. Figure 1 The conductive textile fabric shown.
[0206] Example 6
[0207] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is adjusted to 1:0.1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0208] Example 7
[0209] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of nano-titanium dioxide to stearic acid in the stearic acid solution is adjusted to 1:0.3, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0210] Example 8
[0211] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of polyurethane particles, modified nano-titanium dioxide, and calcium stearate is adjusted to 100:6:1.5, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0212] Example 9
[0213] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of polyurethane particles, modified nano-titanium dioxide, and calcium stearate is adjusted to 100:12:1.5, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0214] Example 10
[0215] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass fraction of carboxylated nanowires in the composite binder is adjusted to 1 wt %. The other operating steps and process parameters are exactly the same as those in Example 1.
[0216] Example 11
[0217] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass fraction of carboxylated nanowires in the composite binder is adjusted to 5 wt %. The other operating steps and process parameters are exactly the same as those in Example 1.
[0218] Example 12
[0219] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is adjusted to 1:0.5, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0220] Example 13
[0221] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution is adjusted to 1:1.5, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0222] Example 14
[0223] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion is adjusted to 1:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0224] Example 15
[0225] This embodiment provides a method for preparing a conductive textile fabric. The difference from Example 1 is that the mass ratio of the cross-linked coated graphene to the aniline monomer in the cross-linked coated graphene dispersion is adjusted to 1:4, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0226] The conductive properties and mechanical properties of the conductive textile fabrics prepared in Examples 1-15 were tested. The specific testing steps are as follows:
[0227] (1) Surface resistance
[0228] The surface resistance of the conductive textile fabric sample was tested using a high resistance meter, referring to the national standard GB / T22042-2008 "Test method for surface resistivity of anti-static performance of clothing". The test voltage was a DC voltage of 100±5V, the test temperature was 20±2℃, the relative humidity was 35±5%RH, the fabric sample size was 100mm×100mm, the fabric sample was flat and wrinkle-free, the electrode spacing was 25±0.5mm, and the parallel electrode method was used for testing. Each fabric sample was tested at 5 different positions and the geometric mean was taken.
[0229] (2) Conductivity retention after 50 washes
[0230] The fabric was washed using the washing method provided in the national standard GB / T 8629-2017 "Household Washing and Drying Procedure for Textile Testing", with a washing frequency of 50 times and a washing temperature of 40±3°C. Referring to the national standard GB / T 22042-2008 "Test Method for Surface Resistivity of Antistatic Properties of Clothing", the surface resistance of the fabric samples before and after washing was tested using the above test conditions. The conductivity retention of the fabric samples was calculated based on the surface resistance of the fabric samples before and after washing.
[0231] (3) Tensile strength
[0232] The tensile strength of the conductive textile fabric samples was tested using a universal material testing machine. The national standard GB / T3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)" was used. The size of the fabric sample was 50 mm × 200 mm, the clamp spacing was 100 mm, and the tensile speed was 100 mm / min. When the fabric sample broke, the maximum breaking strength (N) was recorded. According to the breaking strength and the cross-sectional area of the fabric sample (mm 2 )Calculate the tensile strength (MPa) of the fabric sample.
[0233] (4) Interlayer peel strength
[0234] The interlayer peel strength of conductive textile fabric samples was tested using a universal material testing machine. Referencing the textile industry standard FZ / T 80007.1-2006, "Test Method for Peel Strength of Garments Using Adhesive Interlining," the fabric sample size was 25 mm × 150 mm. The peel angle was 180°, and the peel speed was 100 mm / min. Peeling was performed at a constant tensile speed, and the peel force curve was recorded. The interlayer peel strength (N / mm) of the fabric sample was calculated based on the average peel force and sample width.
[0235] Table 1
[0236]
[0237]
[0238] As can be seen from the data in Table 1, the surface resistance of the conductive textile fabrics prepared in Examples 1-5 is much lower than that in Examples 6-15, and the conductivity retention, tensile strength, and interlayer peel strength are much higher than those in Examples 6-15. This shows that the conductive textile fabrics prepared in the present invention have excellent conductive and mechanical properties. This is because the nano-titanium dioxide is uniformly dispersed through appropriate stearic acid modification, and a three-dimensional conductive network is constructed in conjunction with graphene / polyaniline. The incorporation of appropriate carboxylated nanowires and cross-linking with epoxy resin forms an interpenetrating network, which limits the migration of the conductive components.
[0239] The test data from Examples 1, 6, and 7 show that the surface resistance of the conductive textile fabric prepared in Example 1 is much lower than that of Examples 6 and 7, while the conductivity retention, tensile strength, and interlayer peel strength are much higher than those of Examples 6 and 7. This is because the amount of stearic acid added in Examples 6 and 7 was adjusted. In Example 6, the insufficient amount of stearic acid caused nano-titanium dioxide to agglomerate and the conductive network to break, ultimately resulting in an increase in the surface resistance of the conductive textile fabric. In Example 7, the excessive amount of stearic acid weakened the entanglement of the polyurethane molecular chains, resulting in microporous defects and ultimately a decrease in the tensile strength of the conductive textile fabric.
[0240] The test data from Examples 1, 8, and 9 show that the surface resistance of the conductive textile fabric prepared in Example 1 is much lower than that of Examples 8 and 9, while the conductivity retention, tensile strength, and interlayer peel strength are much higher than those of Examples 8 and 9. This is because the amount of modified nano-titanium dioxide added in Examples 8 and 9 was adjusted. In Example 8, the amount of modified nano-titanium dioxide added was too small, resulting in insufficient mechanical reinforcement effect and ultimately a decrease in the tensile strength of the conductive textile fabric. In Example 9, the amount of modified nano-titanium dioxide added was too large, causing the modified nano-titanium dioxide to agglomerate, ultimately resulting in a decrease in the tensile strength of the conductive textile fabric.
[0241] The test data from Examples 1, 10, and 11 show that the surface resistance of the conductive textile fabric prepared in Example 1 is much lower than that of Examples 10 and 11, while the conductivity retention, tensile strength, and interlayer peel strength are much higher than those of Examples 10 and 11. This is because the mass fraction of carboxylated nanowires in the composite binder was adjusted in Examples 10 and 11. In Example 10, the addition of too few carboxylated nanowires resulted in insufficient vertical conductive paths, ultimately increasing the surface resistance of the conductive textile fabric. In Example 11, the addition of too many carboxylated nanowires resulted in stress concentration, ultimately decreasing the interlayer peel strength of the conductive textile fabric.
[0242] The test data from Examples 1, 12, and 13 show that the surface resistance of the conductive textile fabric prepared in Example 1 is much lower than that of Examples 12 and 13, while the conductivity retention, tensile strength, and interlayer peel strength are much higher than those of Examples 12 and 13. This is because the mass ratio of activated graphene to dopamine hydrochloride in the dopamine solution was adjusted in Examples 12 and 13. In Example 12, the amount of dopamine used was too low, resulting in incomplete graphene surface coating, ultimately causing a decrease in the tensile strength of the conductive textile fabric. In Example 13, the amount of dopamine used was too high, forming an excessively thick insulating layer on the graphene surface, ultimately increasing the surface resistance of the conductive textile fabric.
[0243] The test data from Examples 1, 14, and 15 show that the surface resistance of the conductive textile fabric prepared in Example 1 is much lower than that of Examples 14 and 15, while the conductivity retention, tensile strength, and interlayer peel strength are much higher than those of Examples 14 and 15. This is because the mass ratio of cross-linked and coated graphene to aniline monomer in the cross-linked and coated graphene dispersion was adjusted in Examples 14 and 15. The insufficient amount of aniline monomer in Example 14 resulted in short polyaniline chains and a discontinuous conductive network, ultimately increasing the surface resistance of the conductive textile fabric. The excessive amount of aniline monomer in Example 15 triggered side reactions, ultimately reducing the tensile strength of the conductive textile fabric.
[0244] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A graphene-based conductive textile fabric, characterized in that: The conductive textile fabric comprises a composite polyurethane base film, an adhesive layer and a modified graphene conductive layer stacked in sequence; The composite polyurethane base film is prepared by mixing polyurethane particles, stearic acid-modified nano-titanium dioxide and lubricant, and then sequentially subjected to melt extrusion and blow molding to form a film; The bonding layer is formed by coating a composite adhesive on the surface of the composite polyurethane base film and then drying and curing it. The composite adhesive includes epoxy resin emulsion, polyvinyl pyrrolidone, curing agent and carboxylated nanowires. The modified graphene conductive layer is formed by coating a modified graphene dispersion on the surface of the bonding layer and then drying, curing and hot pressing. The modified graphene dispersion consists of modified graphene and a composite solvent. The modified graphene is obtained by sequentially subjecting graphene powder to acid activation, dopamine coating modification, glutaraldehyde cross-linking modification and polyaniline monomer polymerization coating modification.
2. The conductive textile fabric according to claim 1, characterized in that: The thickness of the composite polyurethane base film is 30 to 40 μm; The thickness of the bonding layer is 8 to 10 μm; The thickness of the modified graphene conductive layer is 10 to 15 μm.
3. A method for preparing a graphene-based conductive textile fabric according to claim 1 or 2, characterized in that: include: (I) modifying nano-titanium dioxide with stearic acid to obtain modified nano-titanium dioxide, mixing polyurethane particles, the modified nano-titanium dioxide, and a lubricant to obtain a mixture, and sequentially melt-extruding, granulating, and blow-molding the mixture into a film to obtain a composite polyurethane base film; (II) modifying silicon carbide nanowires with hydrogen peroxide and sodium hydroxide to obtain carboxylated nanowires; mixing epoxy resin emulsion, polyvinyl pyrrolidone, carboxylated nanowires, a curing agent, and deionized water to obtain a composite adhesive, coating the composite adhesive on the surface of the composite polyurethane base film, and forming an adhesive layer after drying and curing; (III) activating and modifying the graphene powder with a mixed acid solution, coating it with a dopamine solution, and finally cross-linking it with a glutaraldehyde solution to obtain cross-linked coated graphene; in-situ polymerizing and coating the cross-linked coated graphene with aniline monomer and ammonium persulfate solution to obtain modified graphene; (IV) dispersing the modified graphene in a composite solvent, stirring to obtain a dispersion, coating the dispersion on the surface of the adhesive layer, drying, curing and hot pressing to form a modified graphene conductive layer, thereby obtaining the conductive textile fabric.
4. The preparation method according to claim 3, characterized in that In step (I), the modified nano-titanium dioxide is prepared by the following method: Dissolving stearic acid in anhydrous ethanol, stirring and heating to obtain a stearic acid solution, mixing nano-titanium dioxide and the stearic acid solution, ball-milling, and then filtering, washing and vacuum drying to obtain the modified nano-titanium dioxide; Alternatively, the mixing time of the stearic acid and anhydrous ethanol is 40 to 50 minutes; Alternatively, the temperature of mixing the stearic acid and anhydrous ethanol is 60-70° C.; Alternatively, the mass fraction of stearic acid in the stearic acid solution is 3 to 4 wt%; Alternatively, the mass ratio of the nano-titanium dioxide to the stearic acid in the stearic acid solution is 1:(0.15-0.25); Alternatively, the rotation speed of the mixed ball milling of the nano-titanium dioxide and the stearic acid solution is 250 to 350 rpm; Alternatively, the mixing and ball-milling time of the nano-titanium dioxide and the stearic acid solution is 3 to 4 hours.
5. The preparation method according to claim 3, characterized in that In step (I), the mass ratio of the polyurethane particles, the modified nano-titanium dioxide and the lubricant is 100:(8-10):(1.5-2.5); Or, the lubricant includes calcium stearate and / or zinc stearate; Alternatively, the temperature of mixing the polyurethane particles, the modified nano-titanium dioxide and the lubricant is 130-140° C.; Alternatively, the polyurethane particles, the modified nano-titanium dioxide and the lubricant are mixed for 40 to 50 minutes; Alternatively, the melt extrusion of the mixture is carried out in a screw extruder; Alternatively, the barrel of the screw extruder is divided into a first zone, a second zone, and a third zone with different temperatures along the flow direction of the mixed material; Or, the temperature of the first zone is 165-175°C; Or, the temperature of the second zone is 180-190°C; Or, the temperature of the third zone is 195-205°C; Or, the screw speed of the screw extruder is 35 to 45 rpm; Or, the blow ratio of the blown film is (2.5-3.5):1; Alternatively, the composite polyurethane base film has a thickness of 30 to 40 μm.
6. The preparation method according to claim 3, characterized in that In step (II), the carboxylated nanowires are prepared by the following method: uniformly mixing a hydrogen peroxide solution and a sodium hydroxide solution to obtain a modified solution, adding the silicon carbide nanowires to the modified solution, and transferring the solution to a reactor for high-temperature reaction after ultrasonic dispersion. After the reaction is completed, filtering, washing with deionized water, and vacuum drying are performed to obtain the carboxylated nanowires; Or, the mass fraction of the hydrogen peroxide solution is 6 to 8 wt%; The mass fraction of the sodium hydroxide solution is 7 to 9 wt%; The volume ratio of the hydrogen peroxide solution to the sodium hydroxide solution is 1:(1.3-1.5); The mass ratio of the silicon carbide nanowires to the modified solution is 1:(30-40); The ultrasonic power of the silicon carbide nanowires in the modified solution is 300 to 400 W; The ultrasonic dispersion time of the silicon carbide nanowires in the modified solution is 40 to 50 minutes; The temperature of the high temperature reaction is 120-130°C; The high temperature reaction time is 5 to 6 hours.
7. The preparation method according to claim 3, characterized in that In step (II), the composite binder is prepared by the following method: Adding epoxy resin emulsion, polyvinyl pyrrolidone and curing agent into deionized water, mixing, stirring and heating to obtain a bonding base liquid; then adding carboxylated nanowires into the bonding base liquid, and ultrasonically dispersing the nanowires to obtain the composite adhesive; Or, the mass ratio of the epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water is (15-17):(1.5-2.5):(3-5):(80-90); The curing agent includes polyetheramine; The epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water are mixed and stirred for 30 to 40 minutes; The temperature of mixing and stirring the epoxy resin emulsion, the polyvinyl pyrrolidone, the curing agent and the deionized water is 40 to 50° C.; The mass fraction of the carboxylated nanowires in the composite binder is 3 to 4 wt %; The composite adhesive is applied by transfer coating; The coating speed of the composite adhesive is 10 to 12 m / min; The drying temperature of the composite adhesive after coating is 70-80°C; The drying time after the composite adhesive is applied is 15 to 25 minutes; The curing temperature is 90-100°C; The curing time is 2 to 3 hours; The thickness of the adhesive layer is 8 to 10 μm.
8. The preparation method according to claim 3, characterized in that In step (III), the cross-linked coated graphene is prepared by the following method: (1) uniformly mixing a nitric acid solution and a sulfuric acid solution to obtain the mixed acid solution, dispersing the graphene powder in the mixed acid solution, mixing, stirring, and heating to react, and after the reaction is completed, centrifuging, washing with alkaline solution, and vacuum drying to obtain activated graphene; (2) dissolving dopamine hydrochloride in a Tris-HCl buffer to obtain a dopamine solution, dispersing the activated graphene in the dopamine solution, mixing and stirring to cause a polymerization reaction, and after the reaction is completed, centrifuging, washing with deionized water, and vacuum drying to obtain a coated graphene with a polydopamine layer on the surface; (3) adding glutaraldehyde to a Tris-HCl buffer to obtain a glutaraldehyde solution, adding the coated graphene to the glutaraldehyde solution, mixing and stirring to cause a cross-linking reaction, and after the reaction is completed, centrifuging, washing with deionized water, and vacuum drying to obtain the cross-linked coated graphene; Or, in step (1), the mass fraction of the nitric acid solution is 65-70wt%; The mass fraction of the sulfuric acid solution is 95-98wt%; The volume ratio of the nitric acid solution to the sulfuric acid solution is 1:(3-4); The ratio of the graphene powder to the mixed acid solution is 1g:(20-30)L; The mixing time of the graphene powder and the mixed acid solution is 2 to 3 hours; The temperature for mixing the graphene powder and the mixed acid solution is 50-60° C. In step (2), the pH value of the Tris-HCl buffer is 8 to 9; The concentration of dopamine hydrochloride in the dopamine solution is 3-4 mg / mL; The mass ratio of the activated graphene to the dopamine hydrochloride in the dopamine solution is 1:(1-1.2); The activated graphene and the dopamine solution are mixed and stirred for 8 to 10 hours; The temperature of mixing and stirring the activated graphene and the dopamine solution is 25-35° C.; In step (3), the mass fraction of glutaraldehyde in the glutaraldehyde solution is 0.5 to 1 wt%; The mass ratio of the coated graphene to the glutaraldehyde in the glutaraldehyde solution is 1:(0.5-0.6); The time for mixing and stirring the coated graphene and the glutaraldehyde solution is 2 to 4 hours; The temperature for mixing and stirring the coated graphene and the glutaraldehyde solution is 25-35°C.
9. The preparation method according to claim 3, characterized in that In step (III), the modified graphene is prepared by the following method: The cross-linked coated graphene is dispersed in a sodium dodecylbenzenesulfonate solution to obtain a cross-linked coated graphene dispersion, a hydrochloric acid solution is added dropwise to the cross-linked coated graphene dispersion to adjust its pH value, an aniline monomer is added to the cross-linked coated graphene dispersion, and the mixture is uniformly mixed to obtain a precursor solution, an ammonium persulfate solution is added dropwise to the precursor solution under stirring to cause a monomer polymerization reaction, and after the reaction is completed, the mixture is centrifuged, washed with deionized water, and vacuum dried to obtain a modified graphene; Or, the mass fraction of sodium dodecylbenzenesulfonate in the sodium dodecylbenzenesulfonate solution is 0.5 to 1 wt%; The concentration of the cross-linked coated graphene in the cross-linked coated graphene dispersion is 0.3 to 0.5 mg / mL; Adding hydrochloric acid solution dropwise into the cross-linked coated graphene dispersion to adjust the pH value thereof to 1-2; The concentration of the hydrochloric acid solution is 1-2 mol / L; The mass ratio of the cross-linked coated graphene in the cross-linked coated graphene dispersion to the aniline monomer is 1:(2-3); The mixing time of the cross-linked coated graphene dispersion and the aniline monomer is 10 to 15 minutes; The mass fraction of the ammonium persulfate solution is 10-12 wt%; The ammonium persulfate solution is added at a rate of 1 to 2 mL / min; The molar ratio of the aniline monomer to the ammonium persulfate in the ammonium persulfate solution is 1:(1-1.1); After all the ammonium persulfate solution is dropped in, continue mixing and stirring for 10 to 15 hours.
10. The preparation method according to claim 3, characterized in that In step (IV), the composite solvent consists of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, anhydrous ethanol and deionized water; Alternatively, the mass fraction of sodium dodecylbenzenesulfonate in the composite solvent is 0.8 to 1 wt %; The mass fraction of polyvinyl pyrrolidone in the composite solvent is 0.3 to 0.5 wt %; The volume ratio of anhydrous ethanol to deionized water in the composite solvent is 1:(2-3); The concentration of the modified graphene in the modified graphene dispersion is 2 to 3 mg / mL; The speed of high-speed stirring of the modified graphene and the composite solvent is 2000-3000 rpm; The time for high-speed stirring of the modified graphene and the composite solvent is 10 to 15 minutes; The modified graphene dispersion is coated by reciprocating spraying; The spraying pressure of the modified graphene dispersion is 0.3-0.4 MPa; The spraying distance of the modified graphene dispersion is 10 to 20 cm; The modified graphene dispersion is sprayed 3 to 5 times; The drying temperature is 50-60°C; The drying time is 5 to 8 minutes; The curing temperature is 90-100°C; The curing time is 3 to 5 minutes; The temperature of the hot pressing is 80-90°C; The hot pressing time is 10 to 20 seconds; The hot pressing pressure is 6-8 MPa; The thickness of the modified graphene conductive layer is 10 to 15 μm.
Citation Information
Patent Citations
Preparation method for coating doped polyaniline on surface of graphene
CN113265090A
Processing technology of anti-scratch wear-resistant 5G high-precision photoelectric integrated circuit board
CN114449747A
High-density amino polymer modified graphene oxide adsorbent as well as preparation method and application thereof
CN115041154A
Graphene conductive fabric and preparation process thereof
CN115352142A
Graphene polymer conductive film and method of manufacturing the same
US20160244577A1